Electrochromic sheet and electrochromic device
By controlling the deformation amount and optimizing the structure during the processing of the electrochromic sheet, the problem of depression in the electrochromic device during processing is solved, and higher machining and stability are achieved.
Patent Information
- Application Number
- CN202380076180.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-04
- Filing Date
- 2023-10-31
- Publication Date
- 2025-06-13
AI Technical Summary
During processing, the existing electrochromic devices are prone to be depressed due to the lamination direction of the gel-like electrolyte layer, which affects its processability.
By controlling the deformation amount when the electrochromic sheet is pressed under specific conditions, the structure of the electrochromic sheet is optimized, including the arrangement of a support layer, an electrolyte layer, an electrochromic layer and a sealing portion, and the use of materials such as curable resin and metal nanoparticles to improve the processability of the electrochromic sheet.
It effectively improves the processability of the electrochromic sheet, reduces deformation and depression of the electrolyte layer during the punching and bending process, and improves the stability and reliability of the product.
Smart Images

Figure CN120153314A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrochromic sheet and an electrochromic device. Background Art
[0002] An electrochromic element is known as an element that utilizes the phenomenon of electrochromism in which a redox reaction is reversibly induced by applying a voltage and the transmittance reversibly changes. For example, by applying a positive voltage to the electrochromic element, it can be colored, and by applying a negative voltage, it can be decolored to become transparent. Therefore, by providing a switch capable of switching between the application of a positive voltage and a negative voltage, the electrochromic element can be colored and decolored at any time.
[0003] Such electrochromic elements can be roughly classified into two layer structures. One is a layer structure in which an electrochromic material and an electrolyte material are mixed, and the other is a multilayer structure in which the electrochromic material and the electrolyte material are formed into respective layers. Further, in the electrochromic element having the latter multilayer structure, the electrochromic material is fixed in a layer form, and thus the charges injected into the electrochromic material undergo an inverse reaction through an external circuit. Thereby, it has the advantage that once colored, it can maintain the colored state until the decoloring drive is performed and the power consumption can be reduced.
[0004] As an electrochromic device using a gel electrolyte, for example, there is an electrochromic device described in Patent Document 1. Patent Document 1 discloses an electrolyte solution containing at least one bifunctional redox dye dissolved in an ionic liquid solvent and having a Tg of less than about -40°C.
[0005] Prior Art Documents
[0006] Patent Documents
[0007] Patent Document 1: International Publication No. 2004 / 001877. Summary of the Invention
[0008] Problems to be Solved by the Invention
[0009] The present inventors have found that an electrochromic device disclosed in Patent Document 1 has a tendency to be easily recessed in the lamination direction of the electrolyte layer during processing because the gel-like electrolyte layer is sealed inside.
[0010] Technical Means for Solving the Problems
[0011] As a result of intensive studies by the present inventors to improve the processability of the electrochromic sheet, it has been found that it is effective to use the amount of deformation when pressing the electrochromic sheet under specific conditions as an index and control this index, thereby completing the present invention.
[0012] According to the present invention, there is provided an electrochromic sheet and related technologies as follows.
[0013] [1] An electrochromic sheet, comprising:
[0014] A support layer;
[0015] An electrolyte layer disposed on the support layer;
[0016] An electrochromic layer disposed on at least one surface of the electrolyte layer; and
[0017] A sealing portion disposed to cover at least the side surface of the electrolyte layer,
[0018] wherein
[0019] The amount of deformation measured in the following step i is 0.01 mm to 0.09 mm.
[0020] Step i: Using this electrochromic sheet, a test piece having the electrolyte layer as the central portion and the sealing portion as the outer edge (with a maximum length of 20 mm or more) is produced, both ends of the test piece are clamped by a clamping portion, the central portion of the test piece is pressed at 30 N for 30 seconds, and the depth difference between the central portion of the test piece before pressing and the central portion of the test piece after pressing is taken as the amount of deformation (mm).
[0021] [2] The electrochromic sheet according to [1], wherein
[0022] The amount of deformation measured in the following step ii is 0.10 mm or less.
[0023] Step ii: Using this electrochromic sheet, a test piece having the electrolyte layer as the central portion and the sealing portion as the outer edge (with a maximum length of 20 mm or more) is produced, both ends of the test piece are clamped by a clamping portion, the central portion of the test piece is pressed at 50 N for 30 seconds, and the depth difference between the central portion of the test piece before pressing and the central portion of the test piece after pressing is taken as the amount of deformation (mm).
[0024] [3] The electrochromic sheet according to [1], wherein
[0025] There is no yield point in the step i.
[0026] [4] The electrochromic sheet according to [2], wherein
[0027] There is no yield point in the step ii.
[0028] [5] The electrochromic sheet according to any one of [1] to [4], wherein
[0029] The electrolyte layer is solid or gel.
[0030] [6] The electrochromic sheet according to any one of [1] to [5], wherein,
[0031] the electrolyte layer contains an adhesive resin.
[0032] [7] The electrochromic sheet according to [6], wherein,
[0033] the adhesive resin contains one or more selected from (meth)acrylic acid urethane, poly(methyl)acrylic acid methyl ester, poly(methyl)acrylic acid ethyl ester, and poly(ethylene oxide) acrylate.
[0034] [8] The electrochromic sheet according to any one of [1] to [7], wherein,
[0035] electrochromic layers are provided on the upper and lower surfaces of the electrolyte layer of the electrochromic sheet, respectively.
[0036] [9] The electrochromic sheet according to any one of [1] to [8], wherein,
[0037] the sealing portion is formed using a sealing material containing a curable resin.
[0038]
[10] The electrochromic sheet according to [9], wherein,
[0039] the curable resin has at least one selected from an ultraviolet reactive functional group and a thermal reactive functional group.
[0040]
[11] The electrochromic sheet according to any one of [1] to
[10] , wherein,
[0041] the electrochromic sheet further includes an electrode layer between the support layer and the electrochromic layer.
[0042]
[12] An electrochromic device using the electrochromic sheet according to any one of [1] to
[11] .
[0043] Advantages of the Invention
[0044] The present invention provides an electrochromic sheet with improved processability. Brief Description of the Drawings
[0045] Figure 1 is a cross-sectional view schematically showing the electrochromic sheet of the first embodiment.
[0046] Figure 2 is a cross-sectional view showing an enlarged electrochromic layer of the electrochromic sheet of the first embodiment.
[0047] Figure 3 is a cross-sectional view schematically showing the electrochromic sheet of the second embodiment.
[0048] Figure 4 It is a perspective view schematically showing the first support layer coated with a sealing material and a conductive paste during the manufacturing process of the second embodiment.
[0049] Figure 5 It is a perspective view of sunglasses equipped with a lens, and the lens has a curved sheet formed by bending the electrochromic sheet of the third embodiment.
[0050] Figure 6 It is a schematic diagram for explaining a method of manufacturing a lens having a curved sheet formed by bending the electrochromic sheet of the third embodiment.
[0051] Figure 7 It is a top view of the electrochromic sheet of the third embodiment.
[0052] Figure 8 It is Figure 7 A longitudinal sectional view along line A-A in the main part of the electrochromic sheet shown.
[0053] Figure 9 It is a top view of a lens having a curved sheet of the third embodiment.
[0054] Figure 10 It is Figure 8 A longitudinal sectional view along line B-B in the main part of the lens shown.
[0055] Figure 11 It is showing Figure 7 The electrochromic sheet shown and Figure 9 A longitudinal sectional view of the electrochromic element included in the lens shown.
[0056] Figure 12 It is a view of the upper die of the mold of the third embodiment.
[0057] Figure 13 It is a view of the lens of the fourth embodiment.
[0058] Figure 14 It is a view of the mold of the fourth embodiment.
[0059] Figure 15 It is a view showing that a curved concave surface is provided in the lower die of the fourth embodiment.
[0060] Figure 16 It is a view showing the displacement-load curves obtained in Example 1-1 and Comparative Example 1-1.
[0061] Figure 17 It is a view showing the light transmission spectrum of the support layer of Example 4-1.
[0062] Figure 18 This is a graph showing the light transmittance spectrum of the support layer in Comparative Example 4-1. Detailed Embodiments
[0063] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings.
[0064] To avoid complication, when there are multiple identical components in the same drawing, sometimes only one of them is labeled with a reference numeral instead of all components. The drawings are for illustrative purposes only. The shapes, size ratios, etc. of the components in the drawings do not necessarily correspond to actual items.
[0065] In this specification, unless otherwise specified, the expression "a to b" in the description of a numerical range means a or more and b or less. For example, "1 to 5 mass%" means "1 mass% or more and 5 mass% or less". Also, the lower limit value and the upper limit value of the numerical range can be arbitrarily combined with the lower limit value and the upper limit value of other numerical ranges, respectively.
[0066] Unless otherwise specified, each of the components and materials exemplified in this specification can be used alone or in combination of two or more.
[0067] In this embodiment, "covering" is not limited to a continuous case and can also mean that a part has a discontinuous portion.
[0068] 1. Electrochromic Sheet
[0069] <First Embodiment>
[0070] [Electrochromic Sheet]
[0071] Figure 1 This is a schematic cross-sectional view showing an example of an embodiment of the electrochromic sheet 100.
[0072] As Figure 1 shown, the electrochromic sheet 100 includes: a laminate (hereinafter, also referred to as "electrochromic element 10") in which an electrolyte layer 4, a first electrochromic layer 3, and a second electrochromic layer 5 are laminated in sequence; a sealing portion 8 covering the side surfaces of the electrochromic element 10; and a pair of support layers (a first support layer 1 and a second support layer 7) sandwiching the upper and lower surfaces of the electrochromic element 10 and the sealing portion 8.
[0073] In other words, the electrochromic sheet 100 includes a first electrochromic layer 3, an electrolyte layer 4, a second electrochromic layer 5, and a second support layer 7 laminated in sequence on the first support layer 1, and the side surfaces of the first electrochromic layer 3, the electrolyte layer 4, and the second electrochromic layer 5 are respectively covered by the sealing portion 8.
[0074] In the present embodiment, the electrochromic sheet 100 further has a first electrode 2 between the first support layer 1 and the first electrochromic layer 3, and a second electrode 6 between the second support layer 7 and the second electrochromic layer 5.
[0075] And, in Figure 1 the electrochromic sheet 100 having an electrochromic element 10 divided by a sealing portion 8 is described, but the electrochromic sheet may also be long and have a plurality of electrochromic elements 10 divided by the sealing portion 8. At this time, by singulating the electrochromic sheet by punching it in the thickness direction corresponding to each electrochromic element 10, the electrochromic sheet 100 as shown in Figure 1 can be produced. For example, when processing an optical lens using the electrochromic sheet 100, it is punched into a shape close to that of the lens in a plan view. The outer edge of the lens is constituted by the sealing portion 8, and the planar region of the electrochromic element 10 corresponds to the viewing region of the lens.
[0076] The deformation amount of the electrochromic sheet 100 of the present embodiment measured in the following step i is 0.01 mm to 0.09 mm.
[0077] Step i: Using the electrochromic sheet 100, a test piece having the electrolyte layer 4 as the central portion and the sealing portion 8 as the outer edge (the maximum length is 20 mm or more) is produced, both ends of the test piece are clamped by the clamping portion, the central portion of the test piece is pressed at 30 N for 30 seconds, and the depth difference between the central portion of the test piece before pressing and the central portion of the test piece after pressing is taken as the deformation amount (mm).
[0078] Thereby, the processability of the electrochromic sheet 100 can be improved. More specifically, for example, even when a load is applied to the electrolyte layer 4 during the punching process of the electrochromic sheet 100, when it is deformed into a bent shape, during the surface processing when making a prescription lens, or during the clamping during the lens cutting process, deformation and depression of the electrolyte layer 4 can be suppressed.
[0079] Moreover, the electrochromic sheet 100 preferably does not have a yield point in step i. Thereby, good processability can be obtained more stably.
[0080] And, the deformation amount of the electrochromic sheet 100 of the present embodiment measured in the following step ii is 0.10 mm or less.
[0081] Step ii: Using the electrochromic sheet 100, a test piece having the electrolyte layer 4 as the central portion and the sealing portion 8 as the outer edge (the maximum length is 20 mm or more) is produced, both ends of the test piece are clamped by the clamping portion, the central portion of the test piece is pressed at 50 N for 30 seconds, and the depth difference between the central portion of the test piece before pressing and the central portion of the test piece after pressing is taken as the deformation amount (mm).
[0082] Moreover, the electrochromic sheet 100 preferably does not have a yield point in step ii. Thus, good workability can be obtained more stably.
[0083] In the above steps i and ii, the shape of the test piece is appropriately adjusted according to the shape of the electrolyte layer 4 and the sealing portion 8 covering the side surface of the electrolyte layer 4, but at least the maximum length is 20 mm or more. When the shape of the test piece is a quadrilateral, one side is preferably 20 mm or more and the other side is 30 mm or more. Also, the upper limit value of the shape of the test piece is not particularly limited as long as it does not exceed the workbench of the measuring device. The central portion refers to the region including the center point of the test piece in plan view.
[0084] The electrochromic sheet 100 satisfying the above conditions can be realized by optimizing the material and manufacturing steps of the electrolyte layer described later. For example, the type or content of the binder resin of the electrolyte, the use of the ionic liquid described later, and the control of its content can be cited.
[0085] Moreover, the laminate in which the second support layer 7, the second electrode 6, and the second electrochromic layer 5 are laminated in this order is also referred to as "laminate A".
[0086] In the electrochromic sheet 100 of the present embodiment, the second electrochromic layer 5 contains metal nanoparticles 511 and an electrochromic material 521 supported on the metal nanoparticles 511, and can be configured to satisfy the following conditions.
[0087] Condition: When the absorbance of the laminate A at a wavelength of 320 nm is set to α and the absorbance at a wavelength of 295 nm is set to β, (β - α) ≥ 0.8.
[0088] In the laminate A of the present embodiment, almost no difference in absorbance at a wavelength of 320 nm is observed before and after the loading of the electrochromic material 521, and an increase in absorbance can be observed at a wavelength of 295 nm. Therefore, in the present embodiment, the loading amount of the electrochromic material 521 is controlled by determining the difference in absorbance of the laminate A at wavelengths of 320 nm and 295 nm. As a result, it is speculated that good color display properties can be obtained stably.
[0089] In the present embodiment, (β - α) being 0.8 or more means that the loading amount of the electrochromic material of the second electrochromic layer 5 of the present embodiment is more than that of the conventional electrochromic layer.
[0090] (β - α) is preferably 0.9 or more, and more preferably 1.0 or more. Thus, the color display properties can be further improved. Also, α is preferably 1 or less, and more preferably 0.8 or less.
[0091] The electrochromic sheet 100 satisfying the above conditions can be achieved, for example, by adjusting the type and particle size of the metal nanoparticles 511 or controlling the formation method of the second electrochromic layer 5. Specifically, as described later, examples include controlling the concentration of the sol solution of the metal nanoparticles 511, the stirring conditions, or performing temperature management during drying, surface treatment, and annealing temperature management during pigment adsorption. Regarding temperature management, for example, the drying temperature can be set lower than the conventional temperature, such as 60 to 110 °C; the surface treatment temperature can be set lower than the conventional temperature, such as 80 to 120 °C; the annealing temperature during pigment adsorption can be set lower than the conventional temperature, such as 60 to 110 °C. And the treatment time can be adjusted together with the temperature management. Thus, it is considered that the electrochromic material 521 is easily adsorbed by the metal nanoparticles 511, and the above conditions can be satisfied.
[0092] In addition, as a method for taking out the laminate A from the electrochromic sheet 100, examples include cutting and removing the sealing portion covering the side surface of the electrolyte layer of the electrochromic sheet and then peeling at the interface between the electrolyte layer and the electrochromic layer.
[0093] Moreover, in the present embodiment, the light transmittance of both the first support layer 1 and the second support layer 7 of the electrochromic sheet 100 at a wavelength of 380 nm can be 10% or less, or only one of the first support layer 1 and the second support layer 7 can have a light transmittance of 10% or less at a wavelength of 380 nm while the other does not satisfy this condition. At this time, for example, ultraviolet irradiation can be performed from the support layer side that does not satisfy the light transmittance of 10% or less at a wavelength of 380 nm to photocure the sealing material.
[0094] Hereinafter, each structure will be described.
[0095] [Electrolyte layer]
[0096] The electrolyte layer 4 is disposed between the first electrochromic layer 3 and the second electrochromic layer 5 and contains an electrolyte having ion conductivity.
[0097] The average thickness of the electrolyte layer 4 is not particularly limited, and is preferably set to about 10 μm or more and 100 μm or less, more preferably 20 μm or more and 80 μm or less, and further preferably 30 μm or more and 70 μm or less.
[0098] The electrolyte filled in the electrolyte layer 4 can be either a solid or a liquid. Except for the case where the electrolyte is a low-viscosity liquid, for example, various forms such as gel-like, polymer crosslinked type, and liquid crystal dispersed type can also be adopted. Among them, the electrolyte layer 4 is preferably formed in a gel-like or solid state. Thereby, improvement in the element strength and reliability of the electrochromic element 10 can be achieved.
[0099] As a method of forming the electrolyte layer 4 into a solid state, for example, a method of holding a liquid containing an electrolyte and a solvent in an adhesive resin is preferred. Thereby, both high ionic conductivity and solid strength of the electrolyte layer 4 can be obtained.
[0100] Moreover, as the adhesive resin, a photocurable resin is preferred, for example. Thereby, compared with the case where the solid electrolyte layer 4 is obtained by thermal polymerization or vaporization of a solvent, the solid electrolyte layer 4 can be obtained at a low temperature and in a short time.
[0101] The electrolyte layer 4 of the present embodiment preferably contains an adhesive resin and an electrolyte.
[0102] Hereinafter, the details of each material contained in the electrolyte layer 4 will be described.
[0103] (Electrolyte)
[0104] The electrolyte is not particularly limited, and a solid electrolyte, an ionic liquid, etc. can be used.
[0105] ·Solid electrolyte
[0106] The solid electrolyte is not particularly limited. For example, inorganic ionic salts such as alkali metal salts and alkaline earth metal salts, and supported salts of quaternary ammonium salts or acids and bases can be mentioned. Specifically, LiClO 4 , LiBF 4 , LiAsF 6 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 COO, KCl, NaClO 3 , NaCl, NaBF 4 , NaSCN, KBF 4 , Mg(ClO 4 ) 2 and Mg(BF 4 ) 2 etc. can be used alone or in combination of two or more of them.
[0107] ·Ionic liquid
[0108] An ionic liquid is an electrolytic liquid. Among them, an organic ionic liquid has a molecular structure that is liquid in a wide temperature range including room temperature, so it is easy to handle and can be preferably used.
[0109] As the molecular structure of the organic ionic liquid, examples of the cationic component include imidazole derivatives such as N,N-dimethylimidazolium salts, N,N-methylethylimidazolium salts, and N,N-methylpropylimidazolium salts; pyridinium derivatives such as N,N-dimethylpyridinium salts and N,N-methylpropylpyridinium salts; aliphatic quaternary ammonium systems such as trimethylpropylammonium salts, trimethylhexylammonium salts, and triethylhexylammonium salts. And, as the anionic component, considering the stability in the atmosphere, fluorine-containing compounds are preferably used. For example, there can be mentioned BF 4 - , CF 3 SO 3 - , PF 4 - , (CF 3 SO 2 ) 2 N - etc.
[0110] As such an electrolyte material, an ionic liquid obtained by arbitrarily combining the cationic component and the anionic component is preferred.
[0111] The ionic liquid can be directly dissolved in any one of the photopolymerizable monomer, oligomer, and liquid crystal material. Additionally, in the case of poor solubility in these materials, after obtaining a small amount of solution dissolved in a solvent, the solution can be mixed with any one of the photopolymerizable monomer, oligomer, and liquid crystal material to dissolve it.
[0112] As the solvent, for example, there can be mentioned propylene carbonate, acetonitrile, γ-butyrolactone, ethylene carbonate, sulfolane, dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,2-dimethoxyethane, 1,2-ethoxymethoxyethane, polyethylene glycol, alcohols, or their mixed solvents, etc.
[0113] As the above-mentioned ionic liquid, for example, ethylmethylimidazolium tetracyanoborate (manufactured by Merck KGaA), ethylmethylimidazolium bis(trifluoromethanesulfonyl)imide (manufactured by Kanto Chemical Co., Inc.), ethylmethylimidazolium tris(pentafluoroethyl)trifluorophosphate (manufactured by Merck KGaA), ethylmethylimidazolium bis(fluorosulfonyl)imide (manufactured by Kanto Chemical Co., Inc.), ethylmethylimidazolium diethylphosphate (manufactured by Tokyo Chemical Industry Co., Ltd.), butylmethylimidazolium hexafluorophosphate (manufactured by Tokyo Chemical Industry Co., Ltd.), ethylmethylimidazolium trifluoromethanesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.), ethylmethylimidazolium acetate (manufactured by Tokyo Chemical Industry Co., Ltd.), ethylmethylimidazolium tricyanomethanide (manufactured by Tokyo Chemical Industry Co., Ltd.), ethylmethylimidazolium dicyanamide (manufactured by Tokyo Chemical Industry Co., Ltd.), methyloctylimidazolium hexafluorophosphate (manufactured by Tokyo Chemical Industry Co., Ltd.), methylpropylpyrrolidinium bis(fluorosulfonyl)imide (manufactured by Kanto Chemical Co., Inc.), butylmethylimidazolium tetrafluoroborate (manufactured by Tokyo Chemical Industry Co., Ltd.), butylmethylimidazolium bis(trifluoromethanesulfonyl)imide (manufactured by Tokyo Chemical Industry Co., Ltd.), hexylmethylimidazolium bis(trifluoromethylsulfonyl)imide (manufactured by Kanto Chemical Co., Inc.), allylbutylimidazolium tetrafluoroborate (manufactured by Kanto Chemical Co., Inc.), etc. These can be used alone or in combination of two or more. Among them, ethylmethylimidazolium bis(fluorosulfonyl)imide, ethylmethylimidazolium tetracyanoborate, ethylmethylimidazolium bis(trifluoromethanesulfonyl)imide, ethylmethylimidazolium tris(pentafluoroethyl)trifluorophosphate, and allylbutylimidazolium tetrafluoroborate are preferred, and ethylmethylimidazolium bis(fluorosulfonyl)imide is more preferred.
[0114] The content of the above-mentioned ionic liquid is preferably 55% by mass or more, more preferably 60% by mass or more, based on the total amount of the electrolyte composition constituting the gel electrolyte. When the content of the ionic liquid is 55% by mass or more, a gel electrolyte with higher ionic conductivity while maintaining good processability can be obtained. On the other hand, the upper limit value of the content of the ionic liquid is not particularly limited, and from the aspect of improving processability, it is preferably 98% by mass or less, more preferably 90% by mass or less.
[0115] (Binder resin)
[0116] Examples of the binder resin include one or more selected from (meth)acrylic acid urethane, poly(methyl)acrylate, poly(ethyl)acrylate, and poly(ethylene oxide) acrylate.
[0117] Among the above-mentioned binder resins, a polymer having an acrylic urethane chain is preferred. Even in the case of containing a large amount of ionic liquid, the polymer having an acrylic urethane chain easily exhibits a high elastic modulus, and an electrolyte showing a low displacement amount in a steel ball indentation test can be obtained.
[0118] The content of the polymer having the above-mentioned acrylic urethane chain is preferably 18% by mass to 40% by mass, more preferably 20% by mass to 30% by mass, based on the total amount of the electrolyte composition constituting the gel electrolyte.
[0119] When the content of the polymer having the above-mentioned acrylic urethane chain is 18% by mass or more, a gel electrolyte capable of withstanding deformation during processing can be obtained. On the other hand, when the content of the polymer having the above-mentioned acrylic urethane chain is 40% by mass or less, the color rendering property can be improved while maintaining good processability.
[0120] The molecular weight of the polymer having the above-mentioned acrylic urethane chain is preferably 5000 to 30000, more preferably 8000 to 20000. By setting the molecular weight to the above lower limit value or more, good coatability can be obtained when producing an electrolyte sheet. On the other hand, by setting the molecular weight to the above upper limit value or less, good compatibility can be achieved.
[0121] As commercially available products of the polymer having an acrylic urethane chain, for example, UXF4002 (Nippon Kayaku Co., Ltd.), UXT6100 (Nippon Kayaku Co., Ltd.), UX4101 (Nippon Kayaku Co., Ltd.), UX3204 (Nippon Kayaku Co., Ltd.), UX6101 (Nippon Kayaku Co., Ltd.), UX5000 (Nippon Kayaku Co., Ltd.), UN-350 (Negami Chemical Industrial Co., Ltd.), UN-5590 (Negami Chemical Industrial Co., Ltd.), UN-7700 (Negami Chemical Industrial Co., Ltd.), UN-9200A (Negami Chemical Industrial Co., Ltd.), UN-6303PR (Negami Chemical Industrial Co., Ltd.), UN-1255 (Negami Chemical Industrial Co., Ltd.), UN-6202PR (Negami Chemical Industrial Co., Ltd.), UN-6305 (Negami Chemical Industrial Co., Ltd.), UN-7600 (Negami Chemical Industrial Co., Ltd.), UN6304 (Negami Chemical Industrial Co., Ltd.), etc. can be cited.
[0122] Further, among the above-mentioned adhesive resins, a polymer having a polymethyl methacrylate (PMMA) chain is preferred. A polymer having a PMMA chain easily exhibits tack even in the case of containing a large amount of ionic liquid, and a gel electrolyte that does not deform during transportation in the production process of an electrolyte sheet in a roll-to-roll manner can be obtained.
[0123] Examples of commercially available products of the polymer having a PMMA chain include MB-1 (manufactured by TOAGOSEI CO., LTD.), MB-1P (manufactured by TOAGOSEI CO., LTD.), Hi-pearl M4501 (manufactured by Negami Kogyo Co., Ltd.), and the like.
[0124] Furthermore, as the adhesive resin, a cross-linked product of a polymer having a polymethyl methacrylate (PMMA) chain is more preferred. The cross-linked product of a polymer having a PMMA chain can use a low-molecular-weight PMMA-based monomer having better compatibility than linear PMMA in the electrolyte composition stage, so the content can be increased and tack can be more easily exhibited.
[0125] Examples of the cross-linked product of a polymer having PMMA include a cross-linked product obtained by subjecting a reactive oligomer or a reactive polymer having a PMMA chain to a cross-linking reaction.
[0126] The reactive oligomer having a PMMA chain is not particularly limited and can be appropriately selected according to the purpose. Examples thereof include macromonomer AA-6 (manufactured by TOAGOSEI CO., LTD.).
[0127] The content of the cross-linked product of the polymer having a polymethyl methacrylate (PMMA) chain is preferably 1% by mass to 20% by mass, and more preferably 5% by mass to 10% by mass, based on the total amount of the electrolyte composition constituting the gel electrolyte.
[0128] [Other Components]
[0129] The other components are not particularly limited and can be appropriately selected according to the purpose. Examples thereof include polymerization initiators.
[0130] The polymerization initiator is not particularly limited and can be appropriately selected according to the purpose. Examples thereof include radical polymerization initiators.
[0131] Examples of the radical polymerization initiator include thermal polymerization initiators, photo polymerization initiators, and the like.
[0132] As a thermal polymerization initiator, for example, azo compounds such as 2,2'-azobisisobutyronitrile, dimethyl-2,2'-azobis(isobutyrate), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis[2-(2-imidazolin-2-yl)propane]; organic peroxides such as 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, bis(4-tert-butylcyclohexyl) peroxydicarbonate, etc. These can be used alone or in combination of two or more.
[0133] As a photopolymerization initiator, for example, ketal-based photopolymerization initiators such as 2,2-dimethoxy-1,2-diphenylethane-1-one; acetophenone-based photopolymerization initiators such as 1-hydroxycyclohexyl phenyl ketone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 4-phenoxydichloroacetophenone, 4-(tert-butyl)dichloroacetophenone; benzoin ether-based photopolymerization initiators such as benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, etc. These can be used alone or in combination of two or more.
[0134] The content of the polymerization initiator is not particularly limited and can be appropriately selected according to the purpose. Preferably, it is 0.001 parts by mass or more and 5 parts by mass or less, more preferably 0.01 parts by mass or more and 2 parts by mass or less, and particularly preferably 0.01 parts by mass or more and 1 part by mass or less, based on 100 parts by mass of all monomer components.
[0135] [Method for manufacturing gel electrolyte]
[0136] When the electrolyte layer 4 is in a gel state, for example, it can be produced as follows.
[0137] First, it can be produced by making a composition solution and using a polymerization reaction such as a cast polymerization method in which the produced composition solution is sandwiched between a mold or a film to polymerize it. The composition solution can mix the ionic liquid or the electrolyte obtained by mixing a solid electrolyte and a solvent, a polymerizable material, an acrylic urethane monomer, and, if necessary, an acrylate monomer having a PEO chain, and, if necessary, an acrylate monomer having a PMMA chain at a desired ratio, and mix the polymerization initiator and other components as needed.
[0138] As another production method, it is also possible to use a method in which the composition solution before polymerization is coated on one electrochromic layer and polymerized by ultraviolet irradiation or heating. Further, it is also possible to use the following method: the supports on which the electrochromic layers are formed face each other while maintaining a gap of 5 μm or more and 150 μm or less, and after filling the composition solution, it is polymerized by ultraviolet irradiation or heating.
[0139] [Electrochromic layer]
[0140] The first electrochromic layer 3 and the second electrochromic layer 5 are respectively disposed on the upper and lower surfaces of the electrolyte layer 4 and are arranged in a manner of sandwiching the electrolyte layer 4, and are layers containing an electrochromic material.
[0141] Figure 2 It is a cross-sectional view showing an enlarged view of the second electrochromic layer 5 of the electrochromic sheet of the present embodiment. As Figure 2 shown, the second electrochromic layer 5 contains metal nanoparticles 511 and an electrochromic material 521. The electrochromic material 521 is supported by the metal nanoparticles 511.
[0142] Hereinafter, the case where the second electrochromic layer 5 contains metal nanoparticles 511 and an electrochromic material 521 will be described. However, even if the first electrochromic layer 3 contains metal nanoparticles 511 and an electrochromic material 521, although the redox functions are different, other structures, effects, etc. are the same.
[0143] (Metal nanoparticles)
[0144] The metal nanoparticles 511 have excellent electrical conductivity and can energize the electrochromic material 521.
[0145] As the metal nanoparticles 511, any metal particles having electrical conductivity may be used. Specifically, for example, one or more selected from tin oxide, titanium oxide, zinc oxide, antimony(V) oxide, zirconium oxide, and yttrium oxide can be cited. Among them, tin oxide and titanium oxide are preferred.
[0146] The average primary particle diameter (hereinafter, also referred to as "particle diameter") of the metal nanoparticles 511 is preferably 1 nm to 100 nm, and more preferably 3 to 8 nm.
[0147] By setting the particle diameter to be above the above lower limit value, good color display and color erasure performance can be obtained. On the other hand, by setting the particle diameter to be below the above upper limit value, the transparency of the second electrochromic layer 5 can be maintained, or the loading amount of the electrochromic material 521 can be increased by increasing the specific surface area.
[0148] The electrochromic material 521 supported by the metal nanoparticles 511 may be one or more compounds.
[0149] In addition, the second electrochromic layer 5 is preferably formed from a sol solution of the metal nanoparticles 511. Thereby, a good haze value can be obtained, or the reflectance can be increased.
[0150] (Electrochromic material 521)
[0151] The electrochromic material 521 is composed of an electrochromic compound that induces a redox reaction through voltage and can reversibly display color and fade.
[0152] As the electrochromic material 521, it can be either an inorganic electrochromic compound or an organic electrochromic compound, and known electrochromic compounds such as those in the pigment system, polymer system, metal complex system, and metal oxide system can be used.
[0153] As the above electrochromic material 521, it can be either an inorganic electrochromic compound or an organic electrochromic compound. Also, a conductive polymer known to exhibit electrochromism can be used.
[0154] The first electrochromic layer 3 and the second electrochromic layer 5 can be appropriately selected from these electrochromic materials 521. Preferably, when one of them uses an electrochromic material 521 with oxidation color development property, the other uses an electrochromic material with reduction color development property.
[0155] As the electrochromic material 521 with oxidation color development property, preferably a polymer obtained by polymerizing an oxidation color development electrochromic composition containing a radically polymerizable compound, and particularly preferably an electrochromic composition containing a radically polymerizable compound having a triarylamine.
[0156] The single - molecule length of the electrochromic material 521 is preferably 5 nm or less.
[0157] (The first electrochromic layer)
[0158] The first electrochromic layer 3 is a layer that contains, as a main material, a material that exhibits coloration through an oxidation reaction and is thereby colored.
[0159] The average thickness of the first electrochromic layer 3 is not particularly limited, preferably about 0.1 μm or more and 30 μm or less, more preferably about 0.4 μm or more and 10 μm or less.
[0160] As the material that exhibits coloration through an oxidation reaction and is contained as a main material in the first electrochromic layer 3, there is no particular limitation. For example, polymers obtained by polymerizing a composition containing a radically polymerizable compound having a triarylamine, bis - acridine compounds, Prussian blue - type complexes, and nickel oxide can be cited, and one or more of them can be used in combination.
[0161] As the polymer obtained by polymerizing a composition containing a radically polymerizable compound having a triarylamine, for example, the polymers described in Japanese Patent Application Laid - Open No. 2016 - 45464, Japanese Patent Application Laid - Open No. 2020 - 138925, etc. can be cited.
[0162] Furthermore, as a Prussian blue type complex, for example, Fe(III) 4 [Fe(II)(CN) 6 ] 3 The material of composition.
[0163] Among them, it is particularly preferable to use a polymer obtained by polymerizing a composition containing a radically polymerizable compound having a triarylamine, because an electrochromic element that can be operated at a constant voltage and has excellent repetition durability and a high contrast can be obtained.
[0164] Furthermore, the composition containing a radically polymerizable compound having a triarylamine may contain another radically polymerizable compound different from the radically polymerizable compound having a triarylamine, and a polymer obtained by polymerizing the composition may be composed of a crosslinked product obtained by crosslinking these radically polymerizable compounds.
[0165] (Second electrochromic layer)
[0166] The second electrochromic layer 5 is a layer that contains, as a main material, an electrochromic material that changes from transparent to colored by a reduction reaction, and is colored thereby.
[0167] The average thickness of the second electrochromic layer 5 is not particularly limited, but is preferably about 0.2 μm or more and about 5.0 μm or less, and more preferably about 1.0 μm or more and about 4.0 μm or less. If the average thickness is less than 0.2 μm, it may be difficult to obtain color concentration depending on the type of electrochromic material, and if it exceeds 5.0 μm, the manufacturing cost increases, and depending on the type of electrochromic material, the visual recognition may be reduced due to coloring.
[0168] The second electrochromic layer 5 is preferably made of an electrochromic material having the same color tone as that of the first electrochromic layer 3. This can improve the maximum color density, and as a result, can improve the contrast.
[0169] Furthermore, when materials with different hues are used, color mixing can be performed. Furthermore, on both sides of the first electrode 2 and the second electrode 6, the driving voltage in the electrochromic layer 3, the electrolyte layer 4, and the second electrochromic layer 5 can be effectively reduced by coloring through oxidation reaction and reduction reaction, thereby improving the repeated durability of the electrochromic sheet 100.
[0170] The material that is contained as a main material in the second electrochromic layer 5 and that exhibits coloration by a reduction reaction is not particularly limited, and examples thereof include inorganic electrochromic compounds, organic electrochromic compounds, and conductive polymers, and these may be used alone or in combination of two or more.
[0171] As inorganic electrochromic compounds, for example, tungsten oxide, molybdenum oxide, iridium oxide, titanium oxide, etc. can be cited. Among them, tungsten oxide is preferred. Tungsten oxide has a low reduction potential, so the coloration and discoloration potentials are low, and since it is an inorganic material, it has excellent durability, so it can be preferably used.
[0172] And, as organic electrochromic compounds, for example, azobenzene-based, anthraquinone-based, diarylethene-based, dihydropyrene-based, dipyridine-based, styryl-based, styrylspiropyran-based, spirooxazine-based, spirothiophene-based, thioindigo-based, tetrathiafulvalene-based, terephthalic acid-based, triphenylmethane-based, triphenylamine-based, naphthopyran-based, viologen-based, pyrazoline-based, phenazine-based, phenylenediamine-based, phenoxazine-based, phenothiazine-based, phthalocyanine-based, fluoran-based, fulgide-based, benzopyran-based, metallocene-based and other low-molecular organic electrochromic compounds, etc. Among them, viologen-based compounds and dipyridine-based compounds are preferred. These compounds have low coloration and discoloration potentials and exhibit good color values, so they can be preferably used.
[0173] As viologen-based compounds, for example, the compounds described in Japanese Patent No. 3955641, Japanese Patent Application Laid-Open No. 2007-171781, etc. can be cited. And, as dipyridine-based compounds, for example, the compounds described in Japanese Patent Application Laid-Open No. 2007-171781, Japanese Patent Application Laid-Open No. 2008-116718, etc. can be cited.
[0174] As conductive polymers, for example, polypyrrole, polythiophene, polyaniline or their derivatives, etc. can be cited.
[0175] [Support layer]
[0176] The first support layer 1 and the second support layer 7 have the function of supporting the first electrode 2, the first electrochromic layer 3, the electrolyte layer 4, the second electrochromic layer 5, the second electrode 6 and the sealing portion 8. And, it becomes the outermost layer of the electrochromic sheet 100.
[0177] And, the first support layer 1 and the second support layer 7 constitute the outermost layer of the electrochromic sheet 100. That is, at least the first electrochromic layer 3, the electrolyte layer 4, and the second electrochromic layer 5 are not exposed to the outside. Therefore, the first electrochromic layer 3, the electrolyte layer 4, and the second electrochromic layer 5 can be protected from the influence of moisture, oxygen, physical shock / friction, etc. from the outside.
[0178] In the present embodiment, the light transmittance of the first support layer 1 and the second support layer 7 at a wavelength of 380 nm is preferably 10% or less, more preferably 5% or less, and further preferably 1% or less. Thereby, ultraviolet rays can be effectively reduced, and the light resistance of the electrochromic sheet can be improved.
[0179] Moreover, in the present embodiment, the maximum value of the light transmittance of the first support layer 1 and the second support layer 7 at a wavelength of 300 to 380 nm is preferably 10% or less, more preferably 5% or less, and still more preferably 1% or less. Thereby, ultraviolet rays can be effectively reduced, and the light resistance of the electrochromic sheet can be improved.
[0180] Moreover, the light transmittance of the first support layer 1 and the second support layer 7 at a wavelength of 430 nm is preferably 80% or more.
[0181] The first support layer 1 and the second support layer 7 are not particularly limited as long as they are made of a resin material having transparency as the main material, and preferably contain a thermoplastic transparent resin (base resin) as the main material.
[0182] The transparent resin is not particularly limited. For example, acrylic resins, polystyrene resins, polyethylene resins, polypropylene resins, polyester resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polycarbonate resins, polyamide resins, cycloolefin resins, vinyl chloride resins, polyacetal resins, silicone resins, etc. having transparency can be cited, and one or more of these can be used in combination. Among them, polycarbonate resins or polyamide resins are preferred, and polycarbonate resins are particularly preferred. Polycarbonate resins are rich in transparency (light transmittance) and mechanical strength such as rigidity, and also have high heat resistance. Therefore, by using polycarbonate resins in the transparent resin, the transparency, impact resistance, and heat resistance of the first support layer 1 and the second support layer 7 can be improved.
[0183] As the polycarbonate resin, various resins can be used. Among them, aromatic polycarbonate resins are preferred. The aromatic polycarbonate resin has an aromatic ring in its main chain, whereby the first support layer 1 and the second support layer 7 with more excellent strength can be obtained.
[0184] The aromatic polycarbonate resin is synthesized, for example, by an interfacial polycondensation reaction of bisphenol and phosgene, a transesterification reaction of bisphenol and diphenyl carbonate, etc.
[0185] As bisphenol, for example, bisphenol A, bisphenol (modified bisphenol) which is the source of the repeating unit of the polycarbonate shown in the following formula (1A), etc. can be cited.
[0186]
[0187] (In formula (1A), X is an alkyl group, an aromatic group, or a cycloaliphatic group having 1 to 18 carbon atoms, Ra and Rb are each independently an alkyl group having 1 to 12 carbon atoms, m and n are each an integer of 0 to 4, and p is the number of repeating units.)
[0188] In addition, as the bisphenol that is the source of the repeating unit of the polycarbonate represented by formula (1A), specifically, for example, 4,4'-(pentane-2,2-diyl)diphenol, 4,4'-(pentane-3,3-diyl)diphenol, 4,4'-(butane-2,2-diyl)diphenol, 1,1'-(cyclohexanediyl)diphenol, 2-cyclohexyl-1,4-bis(4-hydroxyphenyl)benzene, 2,3-bis(cyclohexyl)-1,4-bis(4-hydroxyphenyl)benzene, 1,1'-bis(4-hydroxy-3-methylphenyl)cyclohexane, 2,2'-bis(4-hydroxy-3-methylphenyl)propane, etc. can be used, and one or more of them can be used in combination.
[0189] Among them, as the polycarbonate resin, it is preferable to use a bisphenol type polycarbonate resin having a skeleton derived from bisphenol as the main component. By using this bisphenol type polycarbonate resin, the first support layer 1 and the second support layer 7 further exhibit excellent strength.
[0190] ·Ultraviolet absorber
[0191] The first support layer 1 and the second support layer 7 preferably further contain an ultraviolet absorber. Thereby, it is easy to improve the light resistance of the electrochromic sheet 100.
[0192] At this time, the ultraviolet absorber can be mixed with the resin material constituting the first support layer 1 and the second support layer 7 to form a resin material containing an ultraviolet absorber and then form the first support layer 1 and the second support layer 7, or it can also be a multilayer structure in which the first support layer 1 and the second support layer 7 each have a layer containing an ultraviolet absorber. When forming the multilayer structure, for example, polycarbonate can be used as a substrate and an ultraviolet absorber can be coated on it to form the first support layer 1 by multilayer formation.
[0193] The ultraviolet absorber is not particularly limited, and known compounds can be used. For example, triazine-based compounds, benzophenone-based compounds, benzotriazole-based compounds, and cyanoacrylate-based compounds can be cited, and one or more of them can be used in combination.
[0194] As triazine compounds, 2 - mono(hydroxyphenyl)-1,3,5 - triazine compounds, 2,4 - bis(hydroxyphenyl)-1,3,5 - triazine compounds, or 2,4,6 - tris(hydroxyphenyl)-1,3,5 - triazine compounds can be cited. Specifically, 2,4 - diphenyl - 6-(2 - hydroxy - 4 - methoxyphenyl)-1,3,5 - triazine, 2,4 - diphenyl - 6-(2 - hydroxy - 4 - ethoxyphenyl)-1,3,5 - triazine, 2,4 - diphenyl-(2 - hydroxy - 4 - propoxyphenyl)-1,3,5 - triazine, 2,4 - diphenyl-(2 - hydroxy - 4 - butoxyphenyl)-1,3,5 - triazine, 2,4 - diphenyl - 6-(2 - hydroxy - 4 - butoxyphenyl)-1,3,5 - triazine, 2,4 - diphenyl - 6-(2 - hydroxy - 4 - hexoxyphenyl)-1,3,5 - triazine, 2,4 - diphenyl - 6-(2 - hydroxy - 4 - octoxyphenyl)-1,3,5 - triazine, 2,4 - diphenyl - 6-(2 - hydroxy - 4 - dodecyloxyphenyl)-1,3,5 - triazine, 2,4 - diphenyl - 6-(2 - hydroxy - 4 - benzyloxyphenyl)-1,3,5 - triazine, 2,4 - diphenyl - 6-(2 - hydroxy - 4 - butoxyethoxy)-1,3,5 - triazine, 2,4 - bis(2 - hydroxy - 4 - butoxyphenyl)-6-(2,4 - dibutoxyphenyl)-1,3 - 5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - methoxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - ethoxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - propoxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - butoxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - hexoxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - octoxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - dodecyloxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - benzyloxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - ethoxyethoxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - butoxyethoxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - propoxyethoxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - methoxycarbonylpropoxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4 - ethoxycarbonylethoxyphenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 4-(1-(2 - ethoxyhexyloxy)-1 - oxopropan - 2 - yloxy)phenyl)-1,3,5 - triazine, 2,4,6 - tris(2 - hydroxy - 3 - methyl - 4 - methoxyphenyl)-1,3,5 - triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxycarbonylethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine, etc.,
[0195] As benzotriazole compounds, for example, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(3-tert-butyl-2-hydroxy-5-methylphenyl)-5-chloro-2H-benzotriazole, 2-(3,5-di-tert-amyl-2-hydroxyphenyl)-2H-benzotriazole, 2-(2H-benzotriazol-2-yl)-4-methyl-6-(3,4,5,6-tetrahydrophthalimidomethyl)phenol, 2-(2-hydroxy-4-octyloxyphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)-2H-benzotriazole, 2-[2'-hydroxy-3,5-bis(1,1-dimethylbenzyl)phenyl]-2H-benzotriazole, 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)4-(1,1,3,3-tetramethylbutyl)phenol], etc. can be cited.,
[0196] When producing the first support layer 1 and the second support layer 7 by extrusion molding, from the viewpoint of good heat resistance, triazine compounds are preferably used, but as long as the heat resistance to the extrusion temperature is sufficient, benzophenone compounds, benzotriazole compounds, and cyanoacrylate compounds can also be used without particular limitation.,
[0197] Examples of commercially available triazine-based ultraviolet absorbers include "TINUVIN 1577", "TINUVIN 460", "TINUVIN 477" (manufactured by BASF Japan Ltd.), "ADK STAB LA-F70" (manufactured by ADEKA CORPORATION), and the like.
[0198] Examples of commercially available benzotriazole-based ultraviolet absorbers having high heat resistance include "ADK STAB LA-31G" (manufactured by ADEKA CORPORATION), and the like.
[0199] The content of the ultraviolet absorber is preferably 0.05 to 8% by mass, more preferably 0.06 to 7% by mass, and still more preferably 0.07 to 6% by mass with respect to the total amount of the first support layer 1. Thereby, the above effects can be more reliably exhibited. By setting the content of the ultraviolet absorber to be not less than the above lower limit value, the ultraviolet absorption effect can be sufficiently obtained. On the other hand, by setting the content of the ultraviolet absorber to be not more than the above upper limit value, the aggregation of the ultraviolet absorber can be suppressed.
[0200] The content of the ultraviolet absorber is preferably 0.05 to 8% by mass, more preferably 0.06 to 7% by mass, and still more preferably 0.07 to 6% by mass with respect to the total amount of the second support layer 7. Thereby, the above effects can be more reliably exhibited. By setting the content of the ultraviolet absorber to be not less than the above lower limit value, the ultraviolet absorption effect can be sufficiently obtained. On the other hand, by setting the content of the ultraviolet absorber to be not more than the above upper limit value, the aggregation of the ultraviolet absorber can be suppressed.
[0201] · Colorant
[0202] Moreover, as long as the first support layer 1 and the second support layer 7 have light transmittance, their colors can be colorless, or any color such as red, blue, or yellow.
[0203] The selection of these colors can be achieved by containing dyes or pigments in the first support layer 1 and the second support layer 7. Examples of such dyes include acid dyes, direct dyes, reactive dyes, and basic dyes, and one or more of them can be used in combination.
[0204] As specific examples of the dye, for example, C.I. Acid Yellow 17, 23, 42, 44, 79, 142, C.I. Acid Red 52, 80, 82, 249, 254, 289, C.I. Acid Blue 9, 45, 249, C.I. Acid Black 1, 2, 24, 94, C.I. Food Black 1, 2, C.I. Direct Yellow 1, 12, 24, 33, 50, 55, 58, 86, 132, 142, 144, 173, C.I. Direct Red 1, 4, 9, 80, 81, 225, 227, C.I. Direct Blue 1, 2, 15, 71, 86, 87, 98, 165, 199, 202, C.I. Direct Black 19, 38, 51, 71, 154, 168, 171, 195, C.I. Reactive Red 14, 32, 55, 79, 249, C.I. Reactive Black 3, 4, 35, etc. can be cited.
[0205] In addition to containing the above-mentioned transparent resin, dye or pigment, the first support layer 1 and the second support layer 7 may contain various additives such as antioxidants, fillers, plasticizers, light stabilizers, ultraviolet absorbers, heat ray absorbers, flame retardants, etc. as needed.
[0206] Moreover, the first support layer 1 and the second support layer 7 may be stretched layers or non-stretched layers.
[0207] Furthermore, the refractive index of the first support layer 1 and the second support layer 7 at a wavelength of 589 nm is preferably 1.3 or more and 1.8 or less, more preferably 1.4 or more and 1.65 or less. By setting the refractive index n1 of the first support layer 1 and the second support layer 7 within the above numerical range, the color display and color erasure functions of the electrochromic sheet 100 can be easily visually recognized.
[0208] The average thickness of the first support layer 1 and the second support layer 7 is preferably set to 0.1 mm or more and 10.0 mm or less, more preferably set to 0.3 mm or more and 5.0 mm or less.
[0209] By setting the average thickness of the first support layer 1 and the second support layer 7 within this range, it is possible to accurately suppress or prevent the electrochromic sheet 100 from being warped while achieving the thinning of the electrochromic sheet 100.
[0210] The first support layer and the second support layer 7 may be made of the same constituent material as each other, and may also be made of different constituent materials. And they may be both stretched materials, or only one of them may be a non-stretched material.
[0211] The refractive indices of the first support layer and the second support layer 7 may be the same as each other or different from each other. And the thicknesses of the first support layer and the second support layer 7 may be the same as each other or different from each other.
[0212] [Sealing portion]
[0213] The sealing portion 8 is used to integrally cover the side surfaces of the electrolyte layer 4 and the first electrochromic layer 3 and the second electrochromic layer 5, prevent moisture or oxygen from invading the electrochromic element 10 from the outside, and bond with the first support layer 1 and the second support layer 7 to prevent peeling of the electrochromic element 10. Also, if the positions of the first electrochromic layer 3 and the second electrochromic layer 5 formed between the opposing first electrode 2 and second electrode 6 are displaced, the color display quality will deteriorate during operation. Therefore, the sealing portion 8 is used to suppress this.
[0214] The average thickness (length in the stacking direction) of the sealing portion 8 can be adjusted according to the average thickness of the electrochromic element 10. For example, it is preferably set to about 20 μm or more and 100 μm or less, and more preferably set to about 40 μm or more and 80 μm or less.
[0215] (Sealing material)
[0216] The sealing portion 8 of the present embodiment is preferably composed of a sealing material having a viscosity (25 °C) of 800 Pa·s or more at a shear rate of 0.1 / s and a viscosity (25 °C) of 200 Pa·s or less at a shear rate of 10 / s. Thereby, in the electrochromic element 10, the adhesion between the sealing portion 8 and the electrolyte layer 4 can be improved. As a result, when the electrochromic sheet 100 of the present embodiment is processed into a desired shape, even if the sealing portion 8 is cut, peeling of the sealing portion 8 from the electrolyte layer 4 is suppressed, and good processing durability can be obtained. Among them, when the electrochromic sheet 100 of the present embodiment is applied to uses such as spectacle lenses, from the aspect of improving the design, it is required that the width of the sealing portion 8 located at the outer edge of the lens be as thin as possible. Therefore, higher adhesion and processability are required. Since the electrochromic sheet 100 of the present embodiment uses a sealing material having a specified viscosity, higher adhesion and processability can be obtained.
[0217] On the other hand, regarding this viscosity, from the aspect of maintaining good coatability of the sealing material in the formation process of the sealing portion 8, the viscosity (25 °C) at a shear rate of 0.1 / s is preferably 2000 Pa·s or less, and the viscosity (25 °C) at a shear rate of 10 / s is preferably 10 Pa·s or more.
[0218] The above viscosity (25 °C) of the sealing material can be controlled by adjusting the type of resin and the content of optional inorganic particles described later. Also, it is preferable to optimize the manufacturing method different from the prior art, such as kneading while suppressing heat generation.
[0219] Regarding the measurement conditions, it is preferably measured by a rotational viscometer or a rheometer using a cone and plate at a specified temperature and shear rate.
[0220] As the components of the sealing material constituting this embodiment, as long as they are transparent insulating materials, there is no particular limitation, and a curable resin and inorganic particles are preferably contained.
[0221] · Curable resin
[0222] As the curable resin, a curable resin having at least one of an ultraviolet-reactive functional group and a heat-reactive functional group is preferred, and a curable resin having a (meth)acryloyl group and / or an epoxy group is more preferred. Examples of the curable resin include (meth)acrylate, epoxy resin, etc.
[0223] As the above (meth)acrylate, there is no particular limitation. For example, (meth)acrylate having a urethane bond, epoxy (meth)acrylate derived from a compound having a glycidyl group and (meth)acrylic acid, etc. can be cited.
[0224] As the above (meth)acrylate having a urethane bond, there is no particular limitation. For example, derivatives of diisocyanates such as isophorone diisocyanate and reactive compounds such as acrylic acid and 2-hydroxyethyl acrylate that undergo an addition reaction with isocyanate can be cited. Their derivatives can be chain-extended with caprolactone or polyol, etc.
[0225] As the above epoxy (meth)acrylate, there is no particular limitation. For example, epoxy (meth)acrylate obtained by reacting an epoxide with (meth)acrylic acid in the presence of a basic catalyst according to a conventional method can be cited. For example, epoxy (meth)acrylate derived from epoxy resins such as bisphenol A type epoxy resin or propylene glycol diglycidyl ether and (meth)acrylic acid can be cited.
[0226] As other (meth)acrylates, for example, one or more selected from methyl methacrylate, tetrahydrofurfuryl methacrylate, benzyl methacrylate, isobornyl methacrylate, 2-hydroxyethyl methacrylate, glycidyl methacrylate, (poly)ethylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, 1,6-hexanediol dimethacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, and glycerol dimethacrylate, etc. can be cited.
[0227] Examples of the above epoxy resins include one or more selected from novolak type epoxy resins such as phenol novolak type epoxy resin and cresol novolak type epoxy resin, bisphenol type epoxy resins such as bisphenol A type epoxy resin and bisphenol F type epoxy resin, aromatic glycidylamine type epoxy resins such as N,N-diglycidylaniline, N,N-diglycidyltoluidine, glycidylamine of diaminodiphenylmethane type, and glycidylamine of aminophenol type, hydroquinone type epoxy resin, biphenyl type epoxy resin, stilbene type epoxy resin, triphenylmethane type epoxy resin, triphenylpropane type epoxy resin, alkyl-modified triphenylmethane type epoxy resin, epoxy resin containing a triazine nucleus, dicyclopentadiene-modified phenol type epoxy resin, naphthol type epoxy resin, naphthalene type epoxy resin, phenol aralkyl type epoxy resin having a phenylene skeleton and / or a biphenylene skeleton, naphthol aralkyl type epoxy resin having a phenylene skeleton and / or a biphenylene skeleton, etc., alicyclic epoxy resins such as vinylcyclohexene dioxide, dicyclopentadiene oxide, and alicyclic diepoxy-adipate, and aliphatic epoxy resins such as these.
[0228] Moreover, as the curable resin, an epoxy / (meth)acrylic resin having at least one or more (meth)acryloyl groups and epoxy groups in one molecule can be used.
[0229] · Inorganic particles
[0230] Examples of the inorganic particles include one or more selected from silica, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, activated clay, alumina, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, calcium silicate, etc.
[0231] The inorganic particles may be particles whose surfaces have been hydrophobically treated. For example, epoxy silane, amino silane, (meth)acryloyl silane, vinyl silane, methylchlorosilane, dimethylpolysiloxane, etc. can be used to hydrophobically treat the surfaces of the inorganic particles by a known method. As the inorganic particles, hydrophobically treated inorganic particles and non-hydrophobically treated inorganic particles can be mixed and used.
[0232] The content of the inorganic particles is 1 to 80% by mass, preferably 3 to 70% by mass, 20 to 60% by mass, based on the total amount of the sealing material.
[0233] · Others
[0234] In addition to the above-mentioned curable resin and inorganic particles, the sealing material of this embodiment may further contain organic particles, polymerization initiators, thermal curing agents, etc.
[0235] As the above-mentioned organic particles, for example, one or more selected from polyester fine particles, polyurethane fine particles, vinyl polymer fine particles, acrylic polymer fine particles, silicone fine particles, core-shell rubber fine particles, etc. can be cited.
[0236] As the above-mentioned polymerization initiators, for example, radical polymerization initiators, cationic polymerization initiators, etc. can be cited.
[0237] As the above-mentioned radical polymerization initiators, photo radical polymerization initiators that generate radicals by light irradiation, thermal radical polymerization initiators that generate radicals by heating, etc. can be cited.
[0238] As the above-mentioned photo radical polymerization initiators, for example, benzophenone-based compounds, acetophenone-based compounds, acylphosphine oxide-based compounds, titanocene-based compounds, oxime ester-based compounds, benzoin ether-based compounds, thioxanthone, etc. can be cited.
[0239] As the above-mentioned thermal radical polymerization initiators, for example, thermal radical polymerization initiators composed of azo compounds, organic peroxides, etc. can be cited. Among them, polymer azo initiators composed of polymer azo compounds are preferred.
[0240] As the above-mentioned cationic polymerization initiator, a photo cationic polymerization initiator can be preferably used.
[0241] The above-mentioned photo cationic polymerization initiator is not particularly limited as long as it generates a protonic acid or a Lewis acid by light irradiation, and can be an ionic photoacid generating type or a non-ionic photoacid generating type.
[0242] As the above-mentioned photo cationic polymerization initiators, for example, onium salts such as aromatic diazonium salts, aromatic onium salts, aromatic sulfonium salts, etc., organometallic complex compounds such as iron-arene complexes, titanocene complexes, arylsilanol-aluminum complexes, etc. can be cited.
[0243] The content of the above-mentioned polymerization initiator is preferably 0.1 to 30 parts by weight, more preferably 1 to 10 parts by weight, relative to 100 parts by weight of the curable resin.
[0244] When the content of the above-mentioned polymerization initiator is above the above lower limit value, the curability of the sealing material is more excellent. On the other hand, when the content of the above-mentioned polymerization initiator is below the above upper limit value, the storage stability of the sealing material is more excellent.
[0245] The above-mentioned thermal curing agent is used to cause the thermal reaction functional groups in the above-mentioned curable resin to react by heating and crosslink them, and has the effect of improving the adhesion and moisture resistance of the curable resin composition after curing.
[0246] Examples of the above-mentioned thermal curing agent include organic acid hydrazides, imidazole derivatives, amine compounds, polyphenolic compounds, acid anhydrides, etc. Among them, solid organic acid hydrazides are preferably used.
[0247] The content of the above-mentioned thermal curing agent is preferably 0.1 to 50 parts by weight, more preferably 1 to 30 parts by weight, based on 100 parts by weight of the curable resin.
[0248] When the content of the above-mentioned polymerization initiator is above the above lower limit value, the curability of the sealing material is more excellent. On the other hand, when the content of the above-mentioned polymerization initiator is below the above upper limit value, the coatability of the sealing material is more excellent.
[0249] In addition, additives such as silane coupling agents, light-shielding agents, reactive diluents, spacers, curing accelerators, defoaming agents, homogenizing agents, polymerization inhibitors, and other coupling agents can be contained as needed.
[0250] (Method for manufacturing a sealing material)
[0251] As a method for manufacturing the sealing material of the present embodiment, for example, a method of mixing a curable resin, inorganic particles, and additives such as a polymerization initiator and / or a thermal curing agent, and a silane coupling agent as needed using a mixer can be mentioned.
[0252] Examples of the above-mentioned mixer include a homogenizing disperser, a homogenizing mixer, a universal mixer, a planetary mixer, a kneader, a three-roll mill, a self-rotating and revolving mixer, etc.
[0253] Thereby, a sealing material having the above-mentioned viscosity (25°C) can be obtained.
[0254] [Electrode]
[0255] The first electrode 2 and the second electrode 6 are respectively electrodes that supply electrons to or receive electrons from between the first electrode 2 and the second electrode 6 when a positive voltage or a negative voltage is applied to the first electrochromic layer 3, the electrolyte layer 4, and the second electrochromic layer 5.
[0256] The first electrode 2 is provided on the surface of the first electrochromic layer 3 on the side opposite to the electrolyte layer 4 side. The second electrode 6 is provided on the surface of the second electrochromic layer 5 on the side opposite to the electrolyte layer 4 side.
[0257] As the constituent materials of the first electrode 2 and the second electrode 6, as long as they are transparent conductive materials, there is no particular limitation. For example, ITO (Indium Tin Oxide), FTO (F-doped Tin Oxide), ATO (Antimony Tin Oxide), IZO (Indium Zinc Oxide), In 2 O 3 , SnO 2 , Sb-containing SnO 2 , Al-containing ZnO and other oxides, Au, Pt, Ag, Cu, or alloys containing them, etc. One or more of them can be used in combination.
[0258] As the manufacturing methods of the first electrode 2 and the second electrode 6 respectively, for example, vacuum evaporation method, sputtering method, ion plating method, etc. can be cited. And as long as it is a method capable of coating and forming the materials of the first electrode 2 and the second electrode 6 respectively, various printing methods such as spin coating method, casting method, microgravure coating method, gravure coating method, bar coating method, roll coating method, wire bar coating method, dip coating method, slot coating method, capillary coating method, spraying method, nozzle coating method, gravure printing method, screen printing method, flexographic printing method, offset printing method, reverse printing method, inkjet printing method, etc. can be cited.
[0259] The average thickness of the first electrode 2 and the second electrode 6 is adjusted to obtain the resistance value required for the redox reaction of the first electrochromic layer 3 and the second electrochromic layer 5. For example, when using ITO as the constituent material of the first electrode 2 and the second electrode 6, it is preferably set independently to about 50 nm or more and 200 nm or less, and more preferably set to about 100 nm or more and 150 nm or less.
[0260] In addition, between the respective layers between the first electrode 2 and the second electrode 6, for example, an insulating porous layer, a protective layer and other intermediate layers can be provided.
[0261] The total thickness of the electrochromic sheet 100 of the present embodiment is not particularly limited, and is preferably 0.3 mm or more and 10.0 mm or less, and more preferably 0.5 mm or more and 5.0 mm or less.
[0262] By setting the total thickness of the electrochromic sheet 100 to be above the above lower limit value, the strength is maintained, and by setting the layer thickness to be below the above upper limit value, the processability of cutting or bending the electrochromic sheet 100 and the like can be improved.
[0263] In addition, each layer included in the electrochromic sheet 100 can be replaced with a layer having any structure that can perform the same function, or other layers can also be included.
[0264] [Function and effect]
[0265] By having the structure as described above, for example, by applying a positive voltage between the first electrode 2 and the second electrode 6, the electrochromic element 10 can be made to display a specified color. On the other hand, by applying a negative voltage between the first electrode 2 and the second electrode 6, the electrochromic element 10 can be decolored and become transparent.
[0266] [Manufacturing method of electrochromic sheet]
[0267] The manufacturing method of the electrochromic sheet of the present embodiment is not limited to the case where there is one electrochromic layer, and can also be applied to the case where there are multiple electrochromic layers.
[0268] Hereinafter, an example of the manufacturing method of the electrochromic sheet 100 will be described.
[0269] The manufacturing method of the electrochromic sheet 100 includes the following steps:
[0270] A step of forming the first electrode 2 on the first support layer 1 and laminating the first electrochromic layer 3 on the first electrode 2;
[0271] A step of forming the second electrode 6 on the second support 7 and forming the second electrochromic layer 5 on the second electrode 6;
[0272] A step of coating a sealing material on the first electrode 2 to surround the outer edge of the first electrochromic layer 3, or coating a sealing material on the second electrode 6 to surround the outer edge of the second electrochromic layer 5;
[0273] A step of preparing the electrolyte layer 4 and making the first electrochromic layer 3 and the second electrochromic layer 5 face each other with the electrolyte layer 4 interposed therebetween and then laminating the first support 1 and the second support 2; and
[0274] A step of curing the sealing material to form the sealing portion 8,
[0275] In the laminating step, the first electrochromic layer 3 and the second electrochromic layer 5 are covered by the sealing material by spreading the sealing material.
[0276] Thus, the electrochromic sheet 100 is obtained.
[0277] <Second Embodiment>
[0278] Figure 3 It is a schematic cross-sectional view showing an example of an embodiment of the electrochromic sheet 200. Figure 3 The electrochromic sheet 200 is Figure 1On the basis of the electrochromic sheet 100, there is also an example in which the first columnar conductive portion 72 and the second columnar conductive portion 62 penetrate through the thickness direction of the sealing portion 8, and other structures / functions are the same as those of the electrochromic sheet 100.
[0279] Moreover, in the electrochromic sheet 200, both the first columnar conductive portion 72 and the second columnar conductive portion 62 are electrically connected to the electrolyte layer 4.
[0280] And, the first columnar conductive portion 72 penetrates through the sealing portion 8 and reaches the second support layer 7 from the first auxiliary electrode layer 71 provided on the first electrode 2. Similarly, the second columnar conductive portion 62 penetrates through the sealing portion 8 and reaches the first support layer 1 from the second auxiliary electrode layer 61 provided on the second electrode 6.
[0281] Hereinafter, the structures / functions different from those of the first embodiment will be described.
[0282] [Electrode]
[0283] The first electrode 2 and the second electrode 6 are electrodes that supply electrons to between the first electrode 2 and the second electrode 6 or receive electrons from between the first electrode 2 and the second electrode 6 when a positive voltage or a negative voltage is applied to the first electrochromic layer 3, the electrolyte layer 4, and the second electrochromic layer 5.
[0284] The first electrode 2 is provided on the surface of the first electrochromic layer 3 on the side opposite to the electrolyte layer 4 side. The second electrode 6 is provided on the surface of the second electrochromic layer 5 on the side opposite to the electrolyte layer 4 side.
[0285] As the constituent materials of these first electrode 2 and second electrode 6, as long as they are conductive materials having transparency, there is no particular limitation. For example, ITO (Indium Tin Oxide), FTO (F-doped Tin Oxide), ATO (Antimony Tin Oxide), IZO (Indium Zinc Oxide), In 2 O 3 , SnO 2 , Sb-containing SnO 2 , Al-containing ZnO and other oxides, Au, Pt, Ag, Cu, or alloys containing them, etc., and one or more of them can be used in combination.
[0286] As methods for manufacturing the first electrode 2 and the second electrode 6 respectively, for example, a vacuum evaporation method, a sputtering method, an ion plating method, etc. can be cited. Moreover, as long as it is a method capable of coating and forming the materials for the first electrode 2 and the second electrode 6 respectively, for example, a spin coating method, a casting method, a microgravure coating method, a gravure coating method, a bar coating method, a roll coating method, a wire bar coating method, a dip coating method, a slot coating method, a capillary coating method, a spraying method, a nozzle coating method, an intaglio printing method, a screen printing method, a flexographic printing method, an offset printing method, an offset printing method, an inkjet printing method, and various other printing methods can be cited.
[0287] The average thicknesses of the first electrode 2 and the second electrode 6 are adjusted to a resistance value required for the redox reaction of the first electrochromic layer 3 and the second electrochromic layer 5. For example, when using ITO as the constituent material of the first electrode 2 and the second electrode 6, they are preferably set independently to about 50 nm or more and 200 nm or less, and more preferably set to about 100 nm or more and 150 nm or less.
[0288] [Columnar conductive part]
[0289] The first columnar conductive part 72 overlaps with the first electrode 2 extending as a wiring from the electrochromic element 10 in a plan view and is provided through the sealing part 8 (refer to Figure 3 ). Moreover, the first columnar conductive part 72 is electrically connected to the first electrode 2 through the first auxiliary electrode layer 71.
[0290] When the outer shape of the electrochromic sheet 200 is processed into a lens shape so that the electrochromic sheet 200 is applicable to, for example, a lens for an eye accessory, the first columnar conductive part 72 is exposed at the end of the lens. Thus, electricity can be supplied to the electrochromic element 10 from the outside through the first columnar conductive part 72.
[0291] Similarly to the first columnar conductive part 72, when the outer shape of the electrochromic sheet 200 is processed into a lens shape so that the electrochromic sheet 200 is applicable to, for example, a lens for an eye accessory, the second columnar conductive part 62 is also exposed at the end of the lens. Thus, electricity can be supplied to the electrochromic element 10 from the outside through the second columnar conductive part 62.
[0292] At this time, for example, the first columnar conductive part 72 can be located on the bridge side of the eye accessory, and the second columnar conductive part 62 can be located on the temple side (the side opposite to the bridge side) of the eye accessory.
[0293] Moreover, the first columnar conductive part 72 and the second columnar conductive part 62 are preferably set independently to have an average thickness of about 10 μm or more and 100 μm or less, more preferably 20 μm or more and 80 μm or less, and further preferably 30 μm or more and 70 μm or less.
[0294] As the constituent materials of the first columnar conductive portion 72 and the second columnar conductive portion 62, any conductive paste having conductivity may be used. Thereby, the adhesion between the first columnar conductive portion 72 and the second columnar conductive portion 62 and the sealing portion 8 can be improved.
[0295] Hereinafter, the details of the conductive paste will be described.
[0296] (Conductive paste)
[0297] The conductive paste of the present embodiment can contain a conductive filler.
[0298] The conductive filler coagulates by subjecting the conductive paste to a curing treatment to form a conductive particle connection structure. Thereby, conductivity is exhibited, and adhesion to the electrolyte layer 4 or the like can be obtained.
[0299] The conductive paste of the present embodiment preferably contains one or more of metal powders selected from gold, silver, copper, platinum, nickel, palladium, and their alloys and conductive carbon fillers as the conductive filler. Among them, from the viewpoints of good conductivity and ease of handling, silver powder is preferably used.
[0300] The shape of the conductive filler is not particularly limited, and for example, spherical, flaky, and scaly shapes can be cited.
[0301] The conductive paste of the present embodiment can contain a curable resin. It preferably has at least one of an ultraviolet reactive functional group and a thermal reactive functional group.
[0302] In the present embodiment, since both the sealing material and the conductive paste are coated in a liquid state and simultaneously enter the curing process, the sealing material and the conductive paste preferably use the same type of curable resin.
[0303] The sealing material and the conductive paste can use the same resin, additives, and manufacturing method except that the insulating property and conductivity of the filler are different.
[0304] From the viewpoints of good coatability and adhesion, the viscosity of the conductive paste is preferably 1 to 1000 Pa·s, more preferably 20 to 80 Pa·s.
[0305] [Other electrodes]
[0306] The first auxiliary electrode layer 71 is laminated as a wiring layer on the surface of the first electrode 2 on the side opposite to the first support layer 1, and is electrically connected to the first columnar conductive portion 72.
[0307] Similarly, the second auxiliary electrode layer 61 is laminated as a wiring layer on the surface of the second electrode 14 on the side opposite to the second support layer 7, and is electrically connected to the second columnar conductive portion 62.
[0308] The resistance values of the first auxiliary electrode layer 71 and the second auxiliary electrode layer 61 are respectively set to be lower than those of the first electrode 2 and the second electrode 14. Therefore, by forming wirings electrically connected to the electrochromic element 10 from the laminate of the first electrode 2 and the first auxiliary electrode layer 71 and the laminate of the second electrode 14 and the second auxiliary electrode layer 61 respectively, more excellent conductivity can be imparted to these wirings (laminates).
[0309] As the constituent materials of the first auxiliary electrode layer 71 and the second auxiliary electrode layer 61, as long as their resistance values are respectively lower than those of the first electrode 2 and the second electrode 14, there is no particular limitation, and materials having excellent conductivity can be used. For example, silver, aluminum, copper, chromium, molybdenum, etc. can be cited, and one or more of them can be used in combination.
[0310] Moreover, the first auxiliary electrode layer 71 and the second auxiliary electrode layer 61 are each preferably set to have an average thickness of about 1 nm or more and 100 nm or less, more preferably about 5 nm or more and 50 nm or less. Thereby, the functions as auxiliary electrodes can be reliably imparted to the first auxiliary electrode layer 71 and the second auxiliary electrode layer 61.
[0311] In addition, intermediate layers such as an insulating porous layer and a protective layer can be provided between the respective layers between the first electrode 2 and the second electrode 6.
[0312] Other structures and effects are the same as those of the first embodiment.
[0313] [Function and effect]
[0314] By having the structure as described above, the electrochromic sheet 200 can, for example, cause the electrochromic element 10 to display a specified color by applying a positive voltage between the first electrode 2 and the second electrode 6. On the other hand, by applying a negative voltage between the first electrode 2 and the second electrode 6, the electrochromic element 10 can be decolored and become transparent.
[0315] [Manufacturing method of electrochromic sheet]
[0316] The manufacturing method of the electrochromic sheet of the present embodiment is not limited to the case where the electrochromic layer is one, and can also be applied to the case where the electrochromic layer is plural.
[0317] Hereinafter, an example of the manufacturing method of the electrochromic sheet 200 will be described.
[0318] The manufacturing method of the electrochromic sheet 200 of the present embodiment includes the following steps:
[0319] A step of disposing the first electrode 2 on the first support layer 1;
[0320] The step of disposing the first electrochromic layer 3 on the first electrode 2;
[0321] The conductive paste is applied to the first electrode 2 in a region that does not overlap with the first electrochromic layer 3 in a plan view, and the sealing material is applied to the first electrode 2 so as to surround the outer periphery of the first electrochromic layer 3 and the outer periphery of the conductive paste;
[0322] The step of curing the sealing material to form the sealing portion 8; and
[0323] The step of curing the conductive paste to form the first columnar conductive portion 72.
[0324] In the present embodiment, it further includes:
[0325] The step of preparing the second support layer 7 and disposing the second electrode 6 on the second support layer 7;
[0326] The step of disposing the second electrochromic layer 5 on the second electrode 6; and
[0327] The electrolyte layer 4 is prepared, and the first support 1 and the second support 2 are bonded with the first electrochromic layer 3 and the second electrochromic layer 5 facing each other with the electrolyte layer 4 interposed therebetween.
[0328] In addition, in the present embodiment, an example in which the first support layer 1 is used as a substrate and the first electrochromic layer 3, the electrolyte layer 4, and the second electrochromic layer 5 are laminated in this order is described, but the manufacturing method of the present invention is not limited thereto.
[0329] Moreover, the electrolyte layer 4 is disposed on the first electrochromic layer 3 in the bonding step, but the electrolyte layer 4 may also be disposed on the first electrochromic layer 3 or the second electrochromic layer 5 in advance.
[0330] Moreover, the arrangements of the first electrode 2 and the second electrode 6 in a plan view are appropriately designed so that the electrolyte layer 4 can be energized.
[0331] Moreover, the order of each step is not limited thereto, and can be appropriately changed within a range that does not impair the effects of the present invention.
[0332] Hereinafter, the detailed content of each step will be described.
[0333] - Step of disposing the first electrode 2 -
[0334] First, the first electrode 2 is disposed on the first support layer 1. The disposing method is not particularly limited. For example, a method of disposing the first electrode 2 by forming a film of a conductive material using a sputtering method can be cited.
[0335] - Step of disposing the first electrochromic layer 3 -
[0336] Next, a first electrochromic layer 3 is disposed on the first electrode 2. The disposition method is not particularly limited. For example, the following method can be cited: A sol solution containing metal nanoparticles is coated on the first electrode 2 and dried, and then an electrochromic material is coated to support the electrochromic material on the metal nanoparticles, thereby forming the first electrochromic layer 3.
[0337] In addition, on the first electrode 2, in addition to the first electrochromic layer 3, a sealing portion 8, a columnar conductive portion, etc. described later are also disposed. Therefore, the first electrochromic layer 3 (the electrochromic element 10 described later) is disposed only in a partial region of the first electrode 2 in a plan view.
[0338] - Coating process of sealing material and conductive paste -
[0339] Figure 4 It is a perspective view of the first support layer 1 coated with the sealing material 81, the conductive paste 222, and the conductive paste 666. In addition, Figure 4 the first electrode 2 is omitted.
[0340] As Figure 4 shown, on the first support layer 1, the conductive paste 222 and the conductive paste 666 are coated in a region that does not overlap with the first electrochromic layer 3 in a plan view, and the sealing material 81 is coated to surround the outer periphery of the first electrochromic layer 3 and the outer peripheries of the conductive paste 222 and the conductive paste 666, respectively.
[0341] The coating order of the conductive paste 222, the conductive paste 666, and the sealing material 81 is not particularly limited.
[0342] By coating the sealing material 81 on the outer periphery of the first electrochromic layer 3, in the subsequent laminating process, the sealing material 81 can be spread out to cover the sides of the electrolyte layer 4, the first electrochromic layer 3, and the second electrochromic layer 5 with the sealing portion 8.
[0343] Moreover, in the present embodiment, the conductive paste 222 becomes the first columnar conductive portion 72 described later, and the conductive paste 666 becomes the second columnar conductive portion 62 described later. And by coating the sealing material 81 to surround the outer peripheries of the conductive paste 222 and the conductive paste 666, the first columnar conductive portion 72 and the second columnar conductive portion 62 that penetrate the sealing portion 8 described later can be formed.
[0344] The coating method is not particularly limited, and a known method can be used.
[0345] - Disposition process of the second electrode 6 -
[0346] In the same manner as the first electrode 2, the second electrode 6 is disposed on the second support layer 7. The disposition method is not particularly limited. For example, a method of disposing the second electrode 6 by forming a film of a conductive material using a sputtering method can be cited.
[0347] - Step of disposing the electrochromic layer 3 of the second electrochromic layer 5 -
[0348] In the same manner as the first electrochromic layer 3, the second electrochromic layer 5 is disposed on the second electrode 6. The disposing method is not particularly limited. For example, the following method can be cited: A sol solution containing metal nanoparticles is coated on the second electrode 6 and dried, and then an electrochromic material is coated to support the electrochromic material on the metal nanoparticles, thereby forming the second electrochromic layer 5.
[0349] - Preparation step of the electrolyte layer 4 -
[0350] The formation method of the electrolyte layer 4 can use the same method as the above method.
[0351] - Laminating step -
[0352] With the electrolyte layer 4 interposed therebetween, the first electrochromic layer 3 and the second electrochromic layer 5 face each other and the first support 1 and the second support 2 are laminated.
[0353] At this time, by spreading the sealing material 81, the sides of the first electrochromic layer 3, the electrolyte layer 4, and the second electrochromic layer 5 are covered with the sealing material 81.
[0354] - Formation step of the sealing portion 8 -
[0355] The sealing material 81 is cured to form the sealing portion 8. The curing of the sealing material 81 can use a known method. For example, it can be cured by performing at least one of light irradiation and heating via the first support layer 1 and the second support layer 7.
[0356] - Formation step of the first columnar conductive portion 72 and the second columnar conductive portion 62 -
[0357] The conductive paste 222 and the conductive paste 666 are cured to form the first columnar conductive portion 72 and the second columnar conductive portion 62, respectively. The curing of the conductive paste 222 and the conductive paste 666 can use a known method. For example, it can be cured by performing at least one of light irradiation and heating via the first support layer 1 and the second support layer 7.
[0358] As the sealing material and the conductive paste 222 and the conductive paste 666, if the same type of curable resin is used, they can be cured simultaneously, and the compatibility between the same type of curable resins is also good. Therefore, the adhesion between the sealing portion 8 and the first columnar conductive portion 72 and the second columnar conductive portion 62 can be further improved.
[0359] In addition, the same type of curable resin refers to, for example, the case where resins having the same main skeleton such as epoxy resin are included.
[0360] Based on the above content, the electrochromic sheet 200 of this embodiment can be obtained.
[0361] 2. Electrochromic device
[0362] The electrochromic device of this embodiment has the above-mentioned electrochromic sheet 100 and electrochromic sheet 200, and may also have other mechanisms as needed.
[0363] There are no particular restrictions on other mechanisms, and they can be appropriately selected according to the use. For example, a power source, a fixing mechanism, a control mechanism, etc. can be cited.
[0364] Examples of electrochromic devices include eyewear, smart glasses, head-mounted displays, AR (Augmented Reality), VR (Virtual Reality), MR (Mixed Reality) display bodies, dimming glasses, binoculars, opera glasses, cycling goggles, watches, electronic paper, electronic photo albums, electronic billboards, dimming covers, electrochromic displays, in-vehicle displays, in-vehicle covers, automotive anti-glare rearview mirrors, etc.
[0365] 3. Lens
[0366] Next, a lens using the above-mentioned electrochromic sheet 100 and electrochromic sheet 200 will be described. In addition, in the third embodiment and the second embodiment, an example of using the electrochromic sheet 150 is given for description, but the electrochromic sheet 100 or electrochromic sheet 200 can also be used instead of the electrochromic sheet 150. And the structure of each layer can be the same as the structure described in the electrochromic sheet 100.
[0367] <Third Embodiment>
[0368] Hereinafter, in this embodiment, in the manufacturing process of a lens in which an optical system sheet member is laminated on the surface, a positioning structure for aligning the sheet member at an appropriate position in the cavity is provided in the sheet member and the cavity. Thereby, the occurrence of misalignment of the sheet member on the lens surface or defects in the injection process of the lens resin material 34 (for example, misalignment, deformation, cracks, etc. of the sheet member) is avoided.
[0369] Hereinafter, as the optical system sheet member, eyeglass lenses to which an electrochromic sheet is applied and sunglasses having such eyeglass lenses are exemplified.
[0370] <Sunglasses>
[0371] Figure 5FIG. 0 is a perspective view showing sunglasses 300 equipped with a lens 30, and the lens 30 has a bent sheet 120 that forms the electrochromic sheet 150 of the present embodiment into a bent shape. Further, hereinafter, when the sunglasses 300 are worn on the user's head, the surface of the lens 30 on the user's eye side is referred to as the back surface, and the surface on the opposite side is referred to as the front surface.
[0372] However, the sunglasses 300 are an example, and it may also be smart glasses, AR, VR, MR display bodies, etc.
[0373] As Figure 5 shown, the sunglasses 300 include a frame 20 and a lens 30 (eyeglass lens). The lens 30 may have a light condensing function or may not have a light condensing function.
[0374] The frame 20 is worn on the user's head and is used to dispose the lens 30 near the front of the user's eyes.
[0375] The frame 20 has a rim portion 21, a bridge portion 22, temple portions 23, and a nose pad portion 24.
[0376] The rim portion 21 is annular, and one is provided for each of the right eye and the left eye, and the lens 30 is installed inside. Thus, the user can visually recognize external information through the lens 30.
[0377] The lens 30 includes a bent sheet 120 that becomes a bent shape by thermally bending the electrochromic sheet 150. The lens 30 can reversibly perform coloring and bleaching at any time by switching the voltage application to the electrochromic element 60 included in the electrochromic sheet 150. And when the lens 30 is installed inside the rim portion 21, connection terminals are respectively provided at positions corresponding to the connection portions connecting the bridge portion 22 and the temple portions 23 in the rim portion 21. These connection terminals are electrically connected to a switch 25 and a battery 26 provided in the temple portions 23 described later through wiring.
[0378] The bridge portion 22 is rod-shaped and is located in front of the upper part of the user's nose when worn on the user's head, and connects a pair of rim portions 21.
[0379] The temple portions 23 are vine-shaped and are connected to the edge portions of each rim portion 21 on the side opposite to the position where the bridge portion 22 is connected. The temple portions 23 hang on the user's ears when worn on the user's head.
[0380] The temple part 23 has a switch 25 exposed in an operable manner on its surface and a built-in battery 26. The switch 25 and the battery 26 are electrically connected to connection terminals provided in the lens 30 through wiring. Thus, by operating the switch 25, it is possible to switch between applying a positive voltage, a negative voltage, and not applying a voltage to the electrochromic element 60 provided in the bending piece 120 of the lens 30.
[0381] When the sunglasses 300 are worn on the user's head, the nose pad part 24 is provided at the edge part corresponding to the user's nose in each frame part 21 and abuts against the user's nose, and at this time, it has a shape corresponding to the abutting part against the user's nose. Thus, the mounted state can be stably maintained.
[0382] There is no particular limitation on the constituent materials of the respective parts constituting the frame 20. For example, various metal materials or various resin materials can be used. In addition, as long as the frame 20 can be worn on the user's head, its shape is not limited to the illustrated shape.
[0383] Moreover, in addition to having the frame 20, the sunglasses 300 may have a frameless structure from the viewpoints of fashionability, light weight, etc.
[0384] In addition, in the present embodiment, the glasses equipped with the lens 30 are applied to the sunglasses 300, but it is not limited thereto. For example, the glasses can be prescription glasses, decorative glasses, goggles for protecting the eyes from the influence of wind, rain, dust, drugs, etc.
[0385] Figure 6 It is a schematic view for explaining a manufacturing method of the lens 30 having the bending piece 120 that forms the electrochromic sheet 150 into a bent shape. Figure 7 It is a top view of the electrochromic sheet 150. Figure 8 It is Figure 7 A longitudinal sectional view along the line A-A of the main part of the electrochromic sheet 150 shown. Figure 9 It is a top view showing the lens 30 having the bending piece 120. Figure 10 It is Figure 9 A longitudinal sectional view along the line B-B of the main part of the lens 30 shown. Figure 11 It is showing Figure 7 The electrochromic sheet 150 shown and Figure 9 A longitudinal sectional view of the electrochromic element 60 provided in the lens 30 shown. Figure 12 It is a view showing the lower die 42 of the die 40, Figure 12 (a) is a bottom view (a view observed from the side constituting the cavity 43), Figure 12 (b) is Figure 12 (a) A longitudinal sectional view along the line C-C. In addition, in Figure 12In (b), the bending piece 120 is shown in order to illustrate the relationship between the bending piece 120 and the lower die 42.
[0386] Hereinafter, for the sake of convenience of explanation, Figure 6 、 Figure 8 、 Figure 10 、 Figure 11 the upper side of Figure 7 、 Figure 9 and the front side near the paper surface of Figure 6 、 Figure 8 、 Figure 10 、 Figure 11 are referred to as "upper", and the lower side of Figure 7 、 Figure 9 and the deep side of the paper surface of Figure 10 are referred to as "lower". And although the bending piece 120 is actually bent, for the sake of convenience of explanation, it is described as being in a flat plate shape in Figure 10 .
[0387] <Lens>
[0388] The lens 30 is a component having translucency and an overall shape of a plate bent outward, and has a resin layer 35 (molding layer) as a lens main body and a bending piece 120 provided on the bending convex surface 36 of the resin layer 35. As described above, the lens 30 may have a light condensing function or may not have a light condensing function.
[0389] The bending piece 120 is a sheet component formed by thermally bending a flat sheet-shaped electrochromic sheet 150 under heating to have a bent shape with a bending convex surface 121 and a bending concave surface 122.
[0390] <Resin layer (lens main body)>
[0391] The resin layer 35 is the lens main body and has translucency, and is located on the back surface of the lens 30. When the lens 30 is given a light condensing function, the resin layer 35 has a light condensing function.
[0392] As the constituent material of the resin layer 35, as long as it is a resin material having translucency, there is no particular limitation, and for example, various curable resins such as various thermoplastic resins, thermosetting resins, and photocurable resins can be cited, and one or two or more of them can be used in combination.
[0393] As the resin material, for example, polyolefins such as polyethylene, polypropylene, ethylene-propylene copolymer, polyvinyl chloride, polystyrene, polyamide, polyimide, polycarbonate, poly-(4-methylpentene-1), ionomer, acrylic resin, polymethyl methacrylate, acrylonitrile-butadiene-styrene copolymer (ABS resin), triacetyl cellulose (TAC), acrylonitrile-styrene copolymer (AS resin), butadiene-styrene copolymer, polyesters such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), polyethers, polyether ketone (PEK), polyether ether ketone (PEEK), polyetherimide, polyacetal (POM), polyphenylene oxide, polysulfone, polyethersulfone, polyphenylene sulfide, polyarylate, aromatic polyester (liquid crystal polymer), polytetrafluoroethylene, polyvinylidene fluoride, other fluorine-based resins, epoxy resin, phenolic resin, urea-formaldehyde resin, melamine resin, silicone resin, polyurethane, etc., or copolymers, mixtures, polymer alloys mainly composed of them. Among them, the resin material preferably composed mainly of the first substrate 11 included in the bending piece 120 described later is of the same type or the same material.
[0394] Thereby, the adhesion between the resin layer 35 and the bending piece 120 can be improved. And since the refractive index difference between the resin layer 35 and the bending piece 120 (the first substrate 11) can be set to be small, light diffuse reflection can be accurately suppressed or prevented between the resin layer 35 and the bending piece 120, and thus light can be transmitted between the resin layer 35 and the bending piece 120 with excellent light transmittance.
[0395] In addition, the refractive index difference between the resin layer 35 and the first substrate 11 included in the bending piece 120 is preferably 0.2 or less, more preferably 0.1 or less. Thereby, the effect obtained by setting the refractive index difference to be small can be more significantly exerted.
[0396] The thickness of the resin layer 35 is not particularly limited. For example, it is preferably 0.5 mm or more and 20.0 mm or less, more preferably 1.0 mm or more and 10.0 mm or less. Thereby, both relatively high strength and light weight can be achieved in the lens 30.
[0397] <Electrochromic sheet>
[0398] The shape of the electrochromic sheet 150 in a plan view will be described.
[0399] As Figure 7As shown, the electrochromic sheet 150 has an EC sheet main body 151 that is substantially rectangular in plan view and positioning corners (notches) 137 that project integrally outward from multiple portions of the outer edge of the EC sheet main body 151. The positioning corners 137 function as one element of a positioning structure 80 when the bent sheet 120 is disposed in the cavity 43 of the mold 40 after the electrochromic sheet 150 is bent. The function of the positioning structure 80 refers to both the function of disposing the bent sheet 120 in an appropriate position of the mold 40 and the function of preventing the bent sheet 120 from shifting due to the injection momentum when injecting the lens resin material 34 into the cavity 43 of the mold 40. As long as it has at least one of these functions, it is sufficient.
[0400] As the shape of the EC sheet main body 151, various shapes such as a rectangular shape, a circular shape, and an elliptical shape can be adopted. Regarding which shape to adopt, it can be appropriately selected. However, considering the trimming shape when obtaining the final lens 30 and the effective utilization rate when obtaining the electrochromic sheet 150 by singulating with the element sealing connection sheet 110 described later, it is preferably a substantially rectangular shape that is horizontally long in plan view.
[0401] In the present embodiment, for example, as Figure 8 shown, it is a horizontally long shape with the upper and lower sides of the circular shape removed in plan view. Specifically, the upper side 155 and the lower side 156 are straight long sides, and the right side 157 and the left side 158 are curved (arcs of the original circular shape) short sides.
[0402] One positioning corner 137 is provided at each of the right side 157 and the left side 158 in a bilaterally symmetric manner, that is, at opposite positions.
[0403] Here, the positioning corner 137 is triangular in plan view. As the shape of the positioning corner 137, in addition to the above, various shapes such as a semicircular shape or a quadrilateral shape can be adopted. Moreover, the shapes or sizes of the two positioning corners 137 can be different. By making the sizes and shapes of the two positioning corners 137 different, it is easy to identify the left and right of the electrochromic sheet 150. And the number of the positioning corners 137 can be multiple. In this case, the number of the left and right positioning corners 137 can be different.
[0404] Next, the laminated structure of the electrochromic sheet 150 will be described.
[0405] As Figure 7 、 Figure 8 shown, the electrochromic sheet 150 includes a first substrate 11, a second substrate 12, a sealing portion 55, an electrochromic element 60, a first conductive portion 17, a second conductive portion 18, a third conductive portion 51, a fourth conductive portion 52, a first auxiliary electrode 15, and a second auxiliary electrode 16.
[0406] Hereinafter, each component constituting the electrochromic sheet 150 will be described.
[0407] The first substrate 11 supports other components including the electrochromic element 60, forms the outermost layer of the electrochromic sheet 150 in which other components including the electrochromic element 60 are disposed between the first substrate 11 and the second substrate 12, and has a function as a protective layer for protecting the electrochromic element 60 and the like.
[0408] In the electrochromic sheet 150, the first substrate 11 and the second substrate 12 form the outermost layer of the electrochromic sheet 150, so that other components including the electrochromic element 60 are not exposed on the surface of the electrochromic sheet 150. Therefore, when the electrochromic sheet 150 is formed into a bent sheet 120 having a bent shape and applied to an object provided in the lens 30, it is possible to reliably prevent sand dust, and even rain, from colliding with the electrochromic element 60, or the electrochromic element 60 from being worn by other components or the like. Therefore, it is possible to reliably prevent the collision or friction from adversely affecting the characteristics of the electrochromic element 60.
[0409] Moreover, the first substrate 11 may be a stretched substrate or an unstretched substrate.
[0410] In addition, the refractive index of the first substrate 11 at a wavelength of 589 nm is preferably 1.3 or more and 1.8 or less, more preferably 1.4 or more and 1.65 or less. By setting the refractive index n1 of the first substrate 11 within the above numerical range, it is possible to accurately suppress or prevent the function of the electrochromic element 60, which can switch between coloring (coloring) and bleaching at any time by ON / OFF switching of the switch 25, from being hindered.
[0411] The average thickness of the first substrate 11 is preferably set to 0.1 mm or more and 10.0 mm or less, more preferably set to 0.3 mm or more and 5.0 mm or less. By setting the average thickness of the first substrate 11 within this range, it is possible to achieve thinning of the electrochromic sheet 150 while accurately suppressing or preventing the electrochromic sheet 150 from being bent.
[0412] The second substrate 12 is disposed opposite to the first substrate 11, supports other components including the electrochromic element 60, forms the outermost layer of the electrochromic sheet 150 in which other components including the electrochromic element 60 are disposed between the first substrate 11 and the second substrate 12, and has a function as a protective layer for protecting the electrochromic element 60.
[0413] In the electrochromic sheet 150, the first substrate 11 and the second substrate 12 form the outermost layer of the electrochromic sheet 150, so that other components including the electrochromic element 60 are not exposed on the surface of the electrochromic sheet 150. Therefore, when the electrochromic sheet 150 is formed into a bent sheet 120 having a bent shape and applied to an object provided in the lens 30, it is possible to reliably prevent sand and dust, and even rain, from colliding with the electrochromic element 60, or the electrochromic element 60 from being worn by other components or the like. Therefore, it is possible to reliably prevent the collision or friction from adversely affecting the characteristics of the electrochromic element 60.
[0414] Moreover, the refractive index of the second substrate 12 at a wavelength of 589 nm may be the same as or different from the refractive index n1 of the first substrate 11, preferably 1.3 or more and 1.8 or less, more preferably 1.4 or more and 1.65 or less. By setting the refractive index n2 of the second substrate 12 within the above numerical range, it is possible to accurately suppress or prevent the function of the electrochromic element 60, which can switch between coloring and bleaching at any time by the ON / OFF switching of the switch 25, from being hindered.
[0415] Moreover, the average thickness of the second substrate 12 may be the same as or different from that of the first substrate 11. For example, it is preferably 0.1 mm or more and 10.0 mm or less, more preferably 0.3 mm or more and 5.0 mm or less. By setting the average thickness of the second substrate 12 within this range, it is possible to reduce the thickness of the electrochromic sheet 150 while accurately suppressing or preventing the electrochromic sheet 150 from being bent.
[0416] The electrochromic element 60 is a light-emitting element that can switch between coloring (coloring) and bleaching at any time by the ON / OFF switching of the switch 25, and is provided in the coloring region 70 divided by the sealing portion 55.
[0417] In the present embodiment, the electrochromic element 60 includes: a first electrode 13 and a first electrochromic layer 63 that are sequentially stacked on the first substrate 11 toward the second substrate 12 side; a second electrode 14 and a second electrochromic layer 64 that are sequentially stacked on the second substrate 12 toward the first substrate 11 side; and an electrolyte layer 65 filled between the first electrochromic layer 63 and the second electrochromic layer 64 (see Figure 11 ).
[0418] The first electrode 13 and the second electrode 14 are electrodes that supply electrons to or receive electrons from between the first electrode 13 and the second electrode 14 when a positive voltage or a negative voltage is applied to the electrochromic element 60 by the switching of the switch 25.
[0419] As the constituent materials of these first electrode 13 and second electrode 14, as long as they are transparent conductive materials, there is no particular limitation. For example, ITO (Indium Tin Oxide), FTO (F-doped Tin Oxide), ATO (Antimony Tin Oxide), IZO (Indium Zinc Oxide), In 2 O 3 , SnO 2 , Sb-containing SnO 2 , Al-containing ZnO and other oxides, Au, Pt, Ag, Cu, or alloys containing them, etc., and one or more of them can be used in combination.
[0420] The average thicknesses of the first electrode 13 and the second electrode 14 are adjusted to the resistance values required for the redox reactions of the electrochromic layers 63 and 64. For example, when using ITO as the constituent materials of the first electrode 13 and the second electrode 14, they are preferably set independently to about 50 nm or more and 200 nm or less, more preferably set to about 100 nm or more and 150 nm or less.
[0421] The first electrochromic layer 63 is a layer containing a material that exhibits coloration through an oxidation reaction as the main material and is thereby colored.
[0422] As the material that exhibits coloration through an oxidation reaction and is contained as the main material in the first electrochromic layer 63, there is no particular limitation. For example, polymers obtained by polymerizing a composition containing a radical polymerizable compound having a triarylamine, bis acridine compounds, Prussian blue type complexes, and nickel oxide can be mentioned, and one or more of them can be used in combination.
[0423] The average thickness of such a first electrochromic layer 63 is not particularly limited, preferably about 0.1 μm or more and 30 μm or less, more preferably about 0.4 μm or more and 10 μm or less.
[0424] The second electrochromic layer 64 is a layer containing an electrochromic material that changes from transparent to colored through a reduction reaction as the main material and is thereby colored.
[0425] The second electrochromic layer 64 preferably uses an electrochromic material having the same hue as the first electrochromic layer 63. Thereby, an increase in the maximum color display concentration can be achieved, and as a result, the contrast can be improved.
[0426] Furthermore, when materials with different hues are used, color mixing can be performed. Furthermore, coloring is performed on both sides of the first electrode 13 and the second electrode 14 by oxidation reaction and reduction reaction, thereby effectively reducing the driving voltage of the electrochromic element 60, thereby improving the repeated durability of the electrochromic element 60.
[0427] The material contained as a main material in the second electrochromic layer 64 and showing color by reduction reaction is not particularly limited, and examples thereof include inorganic electrochromic compounds, organic electrochromic compounds, and conductive polymers, and one or more of these may be used in combination.
[0428] The average thickness of the second electrochromic layer 64 is not particularly limited, but is preferably about 0.2 μm or more and about 5.0 μm or less, and more preferably about 1.0 μm or more and about 4.0 μm or less. If the average thickness is less than 0.2 μm, it may be difficult to obtain color concentration depending on the type of electrochromic material, and if it exceeds 5.0 μm, the manufacturing cost increases, and depending on the type of electrochromic material, the visual recognition may be reduced due to coloring.
[0429] The electrolyte layer 65 is filled between the first electrochromic layer 63 and the second electrochromic layer 64 and contains an electrolyte having ion conductivity.
[0430] In addition, an intermediate layer such as an insulating porous layer or a protective layer may be provided between the layers between the first electrode 13 and the second electrode 14 .
[0431] By setting the electrochromic element 60 to have the above-described structure, it is possible to switch between color development (coloring) and color elimination at any timing by switching the switch 25 ON / OFF.
[0432] The sealing portion 55 is disposed between the first substrate 11 and the second substrate 12 , and has a function of partitioning the coloring region 70 and sealing the electrochromic element 60 in the coloring region 70 .
[0433] As described above, the electrochromic sheet 150 has a structure in which the electrochromic element 60 is arranged in the coloring region 70 defined by the sealing portion 55 between the first substrate 11 and the second substrate 12 .
[0434] Furthermore, in the electrochromic sheet 150 forming the structure, Figures 7 - 10 As shown, when the first electrode 13 and the second electrode 14 of the electrochromic element 60 are respectively used to form the lens 30 using the electrochromic sheet 150 and installed on the inner side of the frame 21, the position corresponding to the connecting portion connecting the bridge portion 22 and the temple portion 23 in the frame 21 exceeds (extends) the colored area 70 divided by the sealing portion 55 and is laid as a patterned wiring.
[0435] As described above, the first conductive portion 17 is disposed so as to overlap with the first electrode 13 that extends as a wiring from the colored region 70 in a plan view, and fills the first hole portion 53, which is a through hole provided through the sealing portion 55. That is, between the first substrate 11, the sealing portion 55, and the first conductive portion 17, the first electrode 13 that extends as a wiring beyond the colored region 70 extends to reach the first conductive portion 17.
[0436] Further, the first conductive portion 17 is electrically connected to the first electrode 13 through the first auxiliary electrode 15, and at an end portion in the thickness direction of the electrochromic sheet 150, when the lens 30 is formed using the electrochromic sheet 150 and mounted inside the frame portion 21, it is exposed at a position on the side of the bridging portion 22 ( Figure 7 , Figure 8 the right side in).
[0437] The second conductive portion 18 is disposed so as to overlap with the second electrode 14 that extends as a wiring from the colored region 70 in a plan view, and fills the second hole portion 54, which is a through hole provided through the sealing portion 55. That is, between the second substrate 12, the sealing portion 55, and the second conductive portion 18, the second electrode 14 that extends as a wiring beyond the colored region 70 extends to reach the second conductive portion 18.
[0438] Further, the second conductive portion 18 is electrically connected to the second electrode 14 via the second auxiliary electrode 16, and at an end portion in the thickness direction of the electrochromic sheet 150, when the lens 30 is formed using the electrochromic sheet 150 and mounted inside the frame portion 21, it is exposed at a position on the side of the lens leg portion 23 ( Figure 7 , Figure 8 the left side in).
[0439] In this way, at the end portion in the thickness direction of the electrochromic sheet 150, as shown by the bridging portion 22 side and the lens leg portion 23 side, the first conductive portion 17 and the second conductive portion 18 are exposed at different positions, and these first conductive portion 17 and second conductive portion 18 are electrically connected to the first electrode 13 and the second electrode 14, respectively.
[0440] Therefore, a voltage can be applied between the first electrode 13 and the second electrode 14 through the first conductive portion 17 and the second conductive portion 18 exposed at the ends in the thickness direction of the electrochromic sheet 150. That is, the first conductive portion 17 and the second conductive portion 18 can be used as terminals when applying a voltage between the first electrode 13 and the second electrode 14. Therefore, after the process of obtaining the bent sheet 120 by the bending process described later or after the process of removing the protective film 50, a voltage is applied between the first electrode 13 and the second electrode 14 through the first conductive portion 17 and the second conductive portion 18, whereby it is possible to easily inspect the electrochromic element 60 provided inside the electrochromic sheet 150. Therefore, it is possible to easily know whether there is a defect in the electrochromic element 60 provided inside the electrochromic sheet 150.
[0441] As the constituent materials of these first conductive portion 17 and second conductive portion 18, as long as they are conductive materials, there is no particular limitation. For example, conductive pastes such as silver paste can be cited. In addition, metals such as gold and copper or their alloys can also be cited.
[0442] Moreover, it is preferable to independently set the average thickness of the first conductive portion 17 and the second conductive portion 18 to about 20 μm or more and 100 μm or less, and more preferably to about 40 μm or more and 80 μm or less. By setting the average thickness of the first conductive portion 17 and the second conductive portion 18 exposed at the ends in the thickness direction of the electrochromic sheet 150 within this range, it is possible to easily use the first conductive portion 17 and the second conductive portion 18 as terminals when applying a voltage between the first electrode 13 and the second electrode 14.
[0443] In addition, in the present invention, as described above, the first conductive portion 17 and the second conductive portion 18 are exposed at different positions at the ends in the thickness direction of the electrochromic sheet 150, and the exposure of these first conductive portion 17 and second conductive portion 18 at the ends is achieved as follows. That is, when obtaining the singulated electrochromic sheet 150 by punching the element sealing connection sheet 110 corresponding to each electrochromic element 60 in its thickness direction, this punching is performed in such a way that it passes through the first conductive portion 17 and the second conductive portion 18 in a top view.
[0444] In addition, the first electrode 13 and the second electrode 14 can be formed at the portion that becomes the positioning corner 137. That is, in the positioning corner 137, the first conductive portion 17 and the second conductive portion 18 are configured to be exposed at the ends in the thickness direction. Thereby, when inspecting the electrochromic element 60, it is easy to grasp the portion where the terminals of the inspection equipment come into contact. And since the positioning corner 137 protrudes outward, the exposed area becomes larger and it is easier to contact the terminals.
[0445] Further, by punching the element sealing connection piece 110 that passes through the first conductive part 17 and the second conductive part 18, the first hole part 53 and the second hole part 54 respectively become hole parts with a part of their wall parts (inner peripheral surfaces) missing. However, in this specification, the hole parts also include the parts where such defects occur.
[0446] Moreover, in the present embodiment, both the first hole part 53 and the second hole part 54 are through holes that penetrate the sealing part 55 along the thickness direction. However, it is not limited thereto. The first hole part 53 can be formed from the first substrate 11 side toward the second substrate 12 side with the sealing part 55 remaining at its bottom, and the second hole part 54 can be formed from the second substrate 12 side toward the first substrate 11 side with the sealing part 55 remaining at its top.
[0447] The third conductive part 51 is arranged to overlap with the first electrode 13 that extends as a wiring from the coloring region 70 in a plan view and fills the through hole, that is, the third hole part 57, which penetrates the sealing part 55 at a position closer to the coloring region 70 side (inner side) than the first hole part 53, that is, at a position between the first conductive part 17 and the electrochromic element 60 in a plan view (refer to Figure 8 ). And this third conductive part 51 is electrically connected to the first electrode 13 through the first auxiliary electrode 15.
[0448] In order to install the lens 30 obtained using the electrochromic sheet 150 (bent sheet 120) inside the frame part 21 as shown in Figure 9 、 Figure 10 and perform trimming processing on its edge part for the purpose of cutting out a cutout corresponding to the shape of the frame part 21 (lens shape), the third conductive part 51 is exposed at a position on the side of the bridge part 22 ( Figure 9 、 Figure 10 the right side in).
[0449] And the fourth conductive part 52 is arranged to overlap with the second electrode 14 that extends as a wiring from the coloring region 70 in a plan view and fills the through hole, that is, the fourth hole part 58, which penetrates the sealing part 55 at a position closer to the coloring region 70 side (inner side) than the second hole part 54, that is, at a position between the second conductive part 18 and the electrochromic element 60 in a plan view (refer to Figure 8 ). And this fourth conductive part 52 is electrically connected to the second electrode 14 through the second auxiliary electrode 16.
[0450] In order to install the lens 30 obtained using the electrochromic sheet 150 (bent sheet 120) inside the frame part 21 as shown in Figure 9 、 Figure 10 and perform trimming processing on its edge part for the purpose of cutting out a cutout corresponding to the shape of the frame part 21, the fourth conductive part 52 is at a position on the side of the lens leg part 23 ( Figure 9, Figure 10 is exposed at the position on the left side in
[0451] Thus, when trimming the edge portion of the lens 30 to form a cutout for installing it inside the frame portion 21, at the end portion in the thickness direction of the electrochromic sheet 150 (bending sheet 120), as shown on the bridge portion 22 side and the lens leg portion 23 side, the third conductive portion 51 and the fourth conductive portion 52 are exposed at different positions, and these third conductive portion 51 and fourth conductive portion 52 are electrically connected to the first electrode 13 and the second electrode 14 respectively.
[0452] Therefore, when installing the trimmed lens 30 (cutout) inside the frame portion 21, these third conductive portion 51 and fourth conductive portion 52 respectively constitute connection terminals that are electrically connected to the switch 25 and the battery 26 provided in the lens leg portion 23 through wiring.
[0453] As the constituent materials of these third conductive portion 51 and fourth conductive portion 52, any conductive material can be used. For example, the same materials as those listed as the constituent materials of the first conductive portion 17 and the second conductive portion 18 can be used.
[0454] Moreover, the average thickness of the third conductive portion 51 and the fourth conductive portion 52 is preferably set to be about 20 μm or more and 100 μm or less, and more preferably about 40 μm or more and 80 μm or less, respectively and independently. In the trimmed lens 30, by setting the average thickness of the third conductive portion 51 and the fourth conductive portion 52 exposed at the end portion in the thickness direction of the electrochromic sheet 150 (bending sheet 120) within this range, the third conductive portion 51 and the fourth conductive portion 52 can be easily used as connection terminals that are electrically connected to the switch 25 and the battery 26 through wiring.
[0455] In addition, through the trimming process of the lens 30, the third hole portion 57 and the fourth hole portion 58 respectively become hole portions with a part of their wall portions (inner circumferential surfaces) missing. However, in this specification, such hole portions with missing parts are also included and referred to as hole portions.
[0456] Furthermore, in this embodiment, both the third hole portion 57 and the fourth hole portion 58 are through holes that penetrate the sealing portion 55 in the thickness direction, but it is not limited thereto. The third hole portion 57 can be formed from the first substrate 11 side toward the second substrate 12 side with the sealing portion 55 remaining at its bottom, and the fourth hole portion 58 can be formed from the second substrate 12 side toward the first substrate 11 side with the sealing portion 55 remaining at its top.
[0457] Also, in the present embodiment, the first hole portion 53, the third hole portion 57, the second hole portion 54, and the fourth hole portion 58 are provided as different hole portions, that is, separately provided in the sealing portion 55, but are not limited thereto. For example, the first hole portion 53 and the third hole portion 57 may be formed as a single hole portion integrally formed without sandwiching the sealing portion 55, and the second hole portion 54 and the fourth hole portion 58 may be formed as a single hole portion integrally formed without sandwiching the sealing portion 55.
[0458] The first auxiliary electrode 15 is laminated on the surface of the first electrode 13, which extends from the colored region 70 as a wiring, on the side opposite to the first substrate 11, and is electrically connected to the first conductive portion 17 formed in the first hole portion 53 and the third conductive portion 51 formed in the third hole portion 57. That is, a first auxiliary electrode 15 is formed between the first electrode 13, the first conductive portion 17, and the third conductive portion 51 to electrically connect them to each other.
[0459] Also, the second auxiliary electrode 16 is laminated on the surface of the second electrode 14, which extends from the colored region 70 as a wiring, on the side opposite to the second substrate 12, and is electrically connected to the second conductive portion 18 formed in the second hole portion 54 and the fourth conductive portion 52 formed in the fourth hole portion 58. That is, a second auxiliary electrode 16 is formed between the second electrode 14, the second conductive portion 18, and the fourth conductive portion 52 to electrically connect them to each other.
[0460] The resistance values of these first auxiliary electrode 15 and second auxiliary electrode 16 are respectively set to be lower than the resistance values of the first electrode 13 and the second electrode 14. Therefore, by forming the wirings electrically connected to the electrochromic element 60 from the laminate of the first electrode 13 and the first auxiliary electrode 15 and the laminate of the second electrode 14 and the second auxiliary electrode 16, respectively, more excellent conductivity can be imparted to these wirings (laminates).
[0461] As the constituent materials of these first auxiliary electrode 15 and second auxiliary electrode 16, as long as the resistance values are respectively lower than those of the first electrode 13 and the second electrode 14, there is no particular limitation, and materials having excellent conductivity can be used. For example, silver, aluminum, copper, chromium, molybdenum, etc. can be cited, and one or more of them can be used in combination.
[0462] Also, the average thicknesses of the first auxiliary electrode 15 and the second auxiliary electrode 16 are preferably set to be 1 nm or more and about 100 nm or less, more preferably 5 nm or more and about 50 nm or less, respectively, independently. Thereby, the functions as auxiliary electrodes can be reliably imparted to the first auxiliary electrode 15 and the second auxiliary electrode 16.
[0463] The total thickness of the electrochromic sheet 150 having the above-described structure is not particularly limited, and is preferably 0.3 mm or more and 10.0 mm or less, more preferably 0.5 mm or more and 5.0 mm or less. Thereby, while imparting excellent strength to the electrochromic sheet 150, when the electrochromic sheet 150 is formed into a bent sheet 120 having a bent shape, excellent thermoformability can be imparted to the electrochromic sheet 150.
[0464] <Bent Sheet>
[0465] The bent sheet 120 is composed of an electrochromic sheet 150 that is joined in a bent shape corresponding to the shape on the bent convex surface 36, which is the outer surface of the resin layer 35, and forms a bent shape. By providing the lens 30 with the bent sheet 120, by switching the voltage applied to the electrochromic element 60 included in the electrochromic sheet 150, a function of reversibly performing color display and color erasure at any time is imparted to the sunglasses 300. Thus, the bent sheet 120 is composed of a material obtained by forming the electrochromic sheet 150 into a bent shape.
[0466] <Manufacturing Method of Lens>
[0467] In the sunglasses 300 (eyeglasses) having the above-described structure, the lens 30 included in the sunglasses 300 is manufactured, for example, by the following manufacturing method of the lens 30.
[0468] Hereinafter, each process of the manufacturing method of the lens 30 having the bent sheet 120 obtained by forming the electrochromic sheet 150 of the present invention into a bent shape will be described in detail.
[0469] The manufacturing method of the electrochromic sheet (bent sheet) 150 will be described, and then the manufacturing method of the lens 30 having the bent sheet 120 will be described.
[0470] <Manufacturing Method of Electrochromic Sheet (Bent Sheet)>
[0471] Sheet Preparation Process:
[0472] Prepare an element-sealed connection sheet 110 having a first substrate 11, a second substrate 12, a sealing portion 55, and electrochromic elements 60, and in which a plurality of electrochromic elements 60 provided corresponding to a coloring region 70 divided by the sealing portion 55 are sandwiched between the first substrate 11 and the second substrate 12. In the element-sealed connection sheet 110, the plurality of electrochromic elements 60 are connected between the first substrate 11 and the second substrate 12 by the sealing portion 55 and are sealed by the first substrate 11, the second substrate 12, and the sealing portion 55.
[0473] Protective Film Arrangement Process:
[0474] By attaching protective films 50 (masking tapes) to both surfaces of the element sealing connection sheet 110 obtained in the sheet preparation process, a connection sheet laminate 210 with protective films 50 attached to both surfaces of the element sealing connection sheet 110 is obtained (refer to Figure 6 (a)).
[0475] Sheet singulation process:
[0476] Next, as shown in Figure 6 (b), in the state where the prepared connection sheet laminate 210, that is, the protective films 50 are attached to both surfaces of the element sealing connection sheet 110, the element sealing connection sheet 110 is blanked in its thickness direction corresponding to each electrochromic element 60, thereby obtaining an element laminate 250 in which the connection sheet laminate 210 is singulated. That is, an electrochromic sheet 150 in a state where protective films 50 are attached to both surfaces and singulated corresponding to each electrochromic element 60 is obtained (refer to Figure 7 、 Figure 8 ).
[0477] The singulated electrochromic sheet 150 integrally has an EC sheet main body 151 having a substantially rectangular shape in plan view and positioning corners 137 protruding outward in the outer peripheral direction from a plurality of portions of the outer edge of the EC sheet main body 151. That is, in the blanking die, a shape for forming the positioning corners 137 is provided.
[0478] As the shape of the EC sheet main body 151, various shapes such as a rectangular shape, a circular shape, and an elliptical shape can be adopted. Regarding which shape to adopt, it can be appropriately selected, but considering the trimming shape when obtaining the final lens 30 and the effective utilization rate when singulating from the above-mentioned element sealing connection sheet 110, it is preferably a substantially rectangular shape that is horizontally long in plan view.
[0479] In the present embodiment, as shown in Figure 7 , the shape of the electrochromic sheet 150 (EC sheet main body 151) is, for example, a horizontally long shape obtained by removing the upper side and the lower side of a circular shape in plan view. Specifically, it is a shape in which the upper side 155 and the lower side 156 are straight long sides and the right side 157 and the left side 158 are curved short sides.
[0480] Sheet bending process:
[0481] Next, as shown in Figure 6 (c), the element laminate 250 singulated in the sheet singulation process is subjected to thermoforming under heating, thereby forming the element laminate 250 into a bent element laminate 220 having a bent concave surface on one side and a bent convex surface on the other side. Thereby, the flat electrochromic sheet 150 in a state where protective films 50 are attached to both surfaces can be formed into a bent sheet 120 having a bent shape.
[0482] This thermal bending process is usually implemented by stamping or vacuum forming.
[0483] The heating temperature (forming temperature) of the element laminate 250 (electrochromic sheet 150) at this time is as described later. In the present embodiment, the electrochromic sheet 150 includes substrates 11 and 12. Considering the melting or softening temperature of the first and second substrates 11 and 12, it is preferably set to about 110°C or higher and 170°C or lower, more preferably set to about 130°C or higher and 160°C or lower. By setting the heating temperature within this range, while preventing the deterioration / deterioration of the electrochromic sheet 150, the electrochromic sheet 150 is softened or in a molten state, whereby the electrochromic sheet 150 can be reliably thermally bent to form a bent sheet 120 having a bent shape.
[0484] In addition, in the case where it is not necessary to process the electrochromic sheet 150 into the bent sheet 120, that is, when the electrochromic sheet 150 is subjected to sheet bending treatment by the recipient, the electrochromic sheet 150 in the form of a flat sheet is of course provided to the recipient.
[0485] Protective film removal process:
[0486] The protective film 50 is peeled off from the bent sheet 120 that has been thermally bent in the sheet bending process.
[0487] Resin layer forming process:
[0488] Next, as shown in Figure 6 (d), the bent sheet 120 is disposed in a mold 40 having a bent concave surface formed in a bent shape. Specifically, as shown in Figure 12 , the bent concave surface 42a of the lower mold 42 of the mold 40 is brought into contact with the bent convex surface 121 of the bent sheet 120. As a positioning structure 80 for appropriately disposing the bent sheet 120 in the mold 40, there are the positioning angle 137 of the bent sheet 120 and the positioning recess 47 of the lower mold 42 described above.
[0489] By fitting the positioning angle 137 of the bent sheet 120 into the positioning recess 47 provided in the lower mold 42, the positioning of the bent sheet 120 can be appropriately performed. In addition, regarding the positioning recess 47, in order to make the arrangement of the arranged positioning angle 137 easy and not easily move after the arrangement, it is preferable to deepen the depth of the positioning recess 47. At this time, since the resin material is filled in the positioning recess 47, the positioning angle 37 is also formed in the lens 30 before trimming. By providing the positioning angle 37 on the lens 30, the positioning recess 47 becomes a retreat channel for injecting resin, and the shear stress is dispersed, thereby reducing damage (such as cracks, etc.) to the bent sheet 120.
[0490] With the bent piece 120 adsorbed to the lower mold 42, the upper mold 41 is installed. For example, using the insert injection molding method or the like, a resin layer 35 mainly composed of a resin material is molded in a cavity 43, which is a space formed by the lower mold 42 and the upper mold 41.
[0491] That is, by cooling and solidifying the constituent material (lens resin material 34) of the resin layer 35 in a molten state while in contact with the bent concave surface of the bent piece 120, the resin layer 35 is molded in a state of being in direct contact with the bent concave surface 122 of the bent piece 120 without an intervening bonding agent layer or the like.
[0492] Thereby, a lens 30 including the heat-bent bent piece 120 and the resin layer 35 is manufactured.
[0493] When injection molding the resin layer 35, the heating temperature (molding temperature) of the constituent material for forming the resin layer 35 in a molten state can be appropriately set according to the type of the constituent material of the resin layer 35. However, when the constituent material of the resin layer 35 and the constituent material of the first substrate 11 included in the later-described bent piece 120 are of the same type or the same material, it is preferably set to about 180 °C or higher and 320 °C or lower, and more preferably set to about 230 °C or higher and 300 °C or lower. By setting the heating temperature within this range, the constituent material of the resin layer 35 in a molten state can be reliably supplied to the bent concave surface 122 of the bent piece 120.
[0494] Also, in the insert injection molding method, it is also preferable to use the injection compression molding method. The injection compression molding method uses a method in which a resin material for forming the resin layer 35 is injected at a low pressure in the mold 40 and then the mold 40 is closed at a high pressure and a compression force is applied to the resin material. Therefore, optical anisotropy caused by molding strain or local orientation of resin molecules during molding is less likely to occur in the resin layer 35 and the lens 30 as molded articles, so it is preferably used. And by controlling the mold compression force uniformly applied to the resin material, the resin material can be cooled at a specified specific volume, so that a resin layer 35 with high dimensional accuracy can be obtained.
[0495] Also, when injecting and compressing the lens resin material 34 in the cavity 43, the bent piece 120 is maintained in an appropriate configuration without causing misalignment or strain or the like through the positioning structure 80 (positioning recess 47, positioning angle 137) and is laminated on the bent convex surface 36 of the resin layer 35. Therefore, a lens 30 with the bent piece 120 having high dimensional accuracy and high quality can be obtained.
[0496] In addition, in the present embodiment, the position of the positioning angle 137 of the bending piece 120 is set at a position orthogonal to the flow direction of the lens resin material 34 (right side 157, left side 158) when disposed in the cavity 43. By setting such a configuration, the bending piece 120 is less likely to shift when the lens resin material 34 is injected into the cavity 43.
[0497] Trimming process:
[0498] As Figure 9 shown, trimming processing for cutting the edge portion of the manufactured lens 30 is performed, whereby a cutout having a shape conforming to the shape of the inner side of the frame portion 21 is produced.
[0499] Lens mounting process:
[0500] Then, by mounting the lens 30 (cutout) on the inner side of the frame portion 21, the sunglasses 300 are obtained.
[0501] <Fourth Embodiment>
[0502] Referring Figures 13 - 15 to, the lens 30 immediately after injection molding and the mold 40 for injection molding (only the main parts are shown) are specifically described. Figure 13 is a view showing the lens 30, showing the state before removing the remaining portions (the first and second trimming resin portions 31, 32) during molding. Figure 13 (a) is a top view, Figure 13 (b) is a front view, Figure 13 (c) is a side view, Figure 13 (d) is a bottom view, Figure 13 (e) is a perspective view. Figure 14 is a cross-sectional view of the mold 40 for injection molding. Figure 15 is a view showing an enlarged view of the surface of the lower mold 42 provided with the bending concave surface 42a.
[0503] The lens 30 has a resin layer 35 as a lens main body and a bending piece 120 provided on the convex surface 38 of the lens. In addition, in the present embodiment, the first trimming resin portion 31 and the second trimming resin portion 32 in a state before removing the remaining portions are provided outside the outer peripheral surface of the resin layer 35.
[0504] The first and second trimming resin portions 31, 32 are portions to be removed by trimming processing after molding. The first trimming resin portion 31 is provided on the gate side. The second trimming resin portion 32 is provided at a position opposite to the first trimming resin portion 31 and serves as a resin accumulation portion.
[0505] As shown in the figure, the first trimming resin portion 31 has a runner resin portion 31a formed in the runner 45 of the mold 40 and a gate resin portion 31b formed in the gate 44. Before the trimming process, the boundary between the gate resin portion 31b and the resin layer 35 is cut off.
[0506] The outer diameter of the resin layer 35 serving as the lens body is, for example, 75 mm in a plan view.
[0507] The thickness of the central portion of the lens body is, for example, 10 mm.
[0508] A plurality of positioning corners (here, the first to eleventh positioning corners 37a to 37k) are provided on the outer peripheral surface of the resin layer 35 serving as the lens body and near the outer peripheral boundary of the lens convex surface 38.
[0509] In a plan view, the positioning corner 137 of the bending piece 120 is overlapped and provided on the fourth positioning corner 37d provided at the three o'clock position in the clockwise direction in the circumferential direction and the ninth positioning corner 37i provided at the nine o'clock position in the clockwise direction in the circumferential direction.
[0510] Reference Figure 14 and Figure 15 the mold 40 will be used to describe the process of injection molding the lens 30 having the above structure. Figure 14 is a cross-sectional view of the mold 40, highlighting the cavity 43. Figure 15 represents the bending concave surface 42a of the lower mold 42.
[0511] The bending concave surface 42a of the lower mold 42 of the mold 40 is brought into close contact with the bending convex surface 121 of the bending piece 120. A plurality of positioning recesses (the first to eleventh positioning recesses 47a to 47k) are provided at positions corresponding to the above-described positioning corners 37 (the first to eleventh positioning corners 37a to 37k) on the outer peripheral edge of the bending concave surface 42a. When the bending piece 120 is brought into close contact with the bending concave surface 42a, the positioning corner 137 of the bending piece 120 is fitted into the positioning recess 47 provided in the lower mold 42 corresponding to the positioning recess (the first to eleventh positioning recesses 47a to 47k) corresponding to the positioning corner 137 of the bending piece 120, and the bending piece 120 is accurately positioned.
[0512] In the present embodiment, in Figure 15 , the ninth positioning recess 47i at the three o'clock position in the clockwise direction in the circumferential direction and the fourth positioning recess 47d at the nine o'clock position in the clockwise direction in the circumferential direction are selected to fit the positioning corner 137 of the bending piece 120. By providing a plurality of positioning recesses (the first to eleventh positioning recesses 47a to 47k) in advance, various bending pieces 120 can be corresponded according to the position of the positioning corner 137 of the bending piece 120.
[0513] The mold 40 is assembled with the bending piece 120 in close contact with the bending concave surface 42a, and the lens resin material 34 is filled into the cavity 43 through the runner 45 and the gate 44. As Figure 13 shown, when the lens 30 is taken out from the mold 40, a molded product having the first and second trimming resin portions 31 can be obtained. Finally, the first and second trimming resin portions 31 are removed to obtain a finished product of the lens 30 with the bending piece 120 laminated on the surface.
[0514] The above describes the present embodiment, but the present invention is not limited thereto.
[0515] For example, each layer constituting the electrochromic element 60 included in the electrochromic sheet 150 can be replaced with layers having any structure that can perform the same function. And the electrochromic sheet 150 may further include other layers such as an intermediate layer between the first and second substrates 11 and 12 and the electrochromic element 60.
[0516] The electrochromic sheet 150 is exemplified as the sheet member laminated on the lens 30, but is not limited thereto. For example, it can also be applied to a polarizing plate for a polarizing lens.
[0517] And, as the positioning structure 80, the combination of the positioning angle 137 of the electrochromic sheet 150 and the positioning recess 47 of the mold 40 is exemplified, but is not intended to be limited thereto. For example, it can be set to omit the positioning recess 47 of the mold 40, set a mark in this part, and align the positioning angle 137 with this mark. At this time, it does not have the function of preventing misalignment when injecting the lens resin material 34.
[0518] And, as the positioning structure 80, the combination of the convex-shaped positioning angle 137 and the concave-shaped positioning recess 47 is exemplified, but is not limited thereto. It can also be a positioning structure 80 in which a concave shape is provided on the electrochromic sheet 150 and a convex shape is provided on the mold 40.
[0519] The above describes the embodiments of the present invention with reference to the drawings, but these are examples of the present invention, and various structures other than the above can also be adopted.
[0520] Hereinafter, an example of a reference mode of the present invention is shown.
[0521] <Reference Mode 1>
[0522] According to Reference Mode 1, by using the absorbance of the electrochromic layer as an index and controlling it, the color display and color erasure performance of the electrochromic sheet can be improved.
[0523] [1] An electrochromic sheet, comprising:
[0524] A laminate comprising a support layer, an electrode layer disposed on the support layer, and an electrochromic layer disposed on the electrode layer;
[0525] an electrolyte layer provided on a surface of the stacked body on the electrochromic layer side; and
[0526] a sealing portion, arranged to cover at least a side surface of the electrolyte layer,
[0527] in,
[0528] The electrochromic layer includes metal nanoparticles and an electrochromic material supported on the metal nanoparticles, and is configured to satisfy the following conditions.
[0529] Condition: When the absorbance of the laminate at a wavelength of 320 nm is set as α and the absorbance at a wavelength of 295 nm is set as β, (β-α)≥0.8.
[0530] [2] The electrochromic sheet according to [1], wherein:
[0531] The metal nanoparticles are one or more selected from tin oxide, titanium oxide, zinc oxide, antimony (V) oxide, zirconium oxide and yttrium oxide.
[0532] [3] The electrochromic sheet according to [1] or [2], wherein:
[0533] The average primary particle size of the metal nanoparticles is 1 nm to 100 nm.
[0534] [4] The electrochromic sheet according to any one of [1] to [3], wherein
[0535] The electrochromic material of the electrochromic layer has reduction color development property.
[0536] [5] The electrochromic sheet according to any one of [1] to [4], wherein
[0537] The sealing portion is formed using a sealing material containing a curable resin.
[0538] [6] The electrochromic sheet according to [5], wherein:
[0539] The curable resin has at least one selected from a UV-reactive functional group and a thermally reactive functional group.
[0540] [7] The electrochromic sheet according to any one of [1] to [6], wherein
[0541] The support layer contains one or more selected from episulfide resins, thiocarbamate resins, methacrylate resins, polycarbonate resins, polyurethane resins, polyamide resins, polyester resins, and cellulose resins.
[0542] [8] The electrochromic sheet according to any one of [1] to [7], wherein
[0543] The electrolyte layer is solid or gel.
[0544] [9] The electrochromic sheet according to any one of [1] to [8], wherein
[0545] The electrochromic layers are respectively provided on the upper and lower surfaces of the electrolyte layer.
[0546]
[10] The electrochromic sheet according to any one of [1] to [9], wherein
[0547] The electrochromic sheet further includes an electrode layer between the support layer and the electrochromic layer.
[0548]
[11] An electrochromic device using the electrochromic sheet according to any one of [1] to
[10] .
[0549] <Reference Mode 2>
[0550] According to Reference Mode 2, a sealing material capable of improving the sealing property of the sealing portion in the electrochromic sheet can be obtained.
[0551] [1] A sealing material constituting the sealing portion of an electrochromic sheet, wherein the electrochromic sheet includes:
[0552] An electrolyte layer;
[0553] A sealing portion provided to cover the side surface of the electrolyte layer; and
[0554] An electrochromic layer provided on at least one surface of the electrolyte layer,
[0555] The viscosity (25°C) of the sealing material at a shear rate of 0.1 / s is 800 Pa·s or more, and the viscosity (25°C) at a shear rate of 10 / s is 200 Pa·s or less.
[0556] [2] The sealing material according to [1], wherein
[0557] The sealing material contains a curable resin.
[0558] [3] The sealing material according to [2], wherein
[0559] The curable resin has at least one selected from ultraviolet-reactive functional groups and heat-reactive functional groups.
[0560] [4] The sealing material according to any one of [1] to [3], wherein
[0561] The sealing material contains inorganic particles.
[0562] [5] The sealing material according to any one of [1] to [4], wherein
[0563] The electrolyte layer of the electrochromic sheet is solid or gel.
[0564] [6] The sealing material according to any one of [1] to [5], wherein
[0565] The electrochromic layers are provided on the upper and lower surfaces of the electrolyte layer of the electrochromic sheet, respectively.
[0566] [7] The sealing material according to any one of [1] to [6], wherein
[0567] The sealing portion integrally covers the side surfaces of the electrolyte layer and the electrochromic layer.
[0568] [8] An electrochromic sheet using the sealing material according to any one of [1] to [7].
[0569] [9] An electrochromic device using the electrochromic sheet according to [8].
[0570] <Reference Mode 3>
[0571] According to Reference Mode 3, by using the light transmittance of the support layer at a wavelength of 380 nm as an index and setting it to 10% or less, it is possible to effectively reduce ultraviolet rays on the shorter wavelength side than blue light and improve the light resistance of the electrochromic sheet.
[0572] [1] An electrochromic sheet, comprising:
[0573] A support layer;
[0574] An electrolyte layer provided on the support layer;
[0575] An electrochromic layer provided on at least one surface of the electrolyte layer; and
[0576] A sealing portion provided to cover at least the side surface of the electrolyte layer, wherein
[0577] The light transmittance of the support layer at a wavelength of 380 nm is 10% or less.
[0578] [2] The electrochromic sheet according to [1], wherein,
[0579] the light transmittance of the support layer at a wavelength of 430 nm is 80% or more.
[0580] [3] The electrochromic sheet according to [1] or [2], wherein,
[0581] the support layer contains an ultraviolet absorber.
[0582] [4] The electrochromic sheet according to any one of [1] to [3], wherein,
[0583] the support layer contains one or more selected from the group consisting of episulfide resins, thiocarbamate resins, acrylic resins, polycarbonate resins, polyurethane resins, polyamide resins, polyester resins, cellulose resins, cycloolefin polymers (COP), cycloolefin copolymers (COC), norbornene resins, and silicone resins.
[0584] [5] The electrochromic sheet according to any one of [1] to [4], wherein,
[0585] the sealing portion is formed using a sealing material containing a thermosetting resin.
[0586] [6] The electrochromic sheet according to [5], wherein,
[0587] the thermosetting resin contains one or more selected from the group consisting of epoxy resins, acrylic resins, phenolic resins, maleimide resins, silicone resins, polyurethane resins, cyanate ester resins, melamine resins, urea resins, and unsaturated polyester resins.
[0588] [7] The electrochromic sheet according to any one of [1] to [6], wherein,
[0589] the electrolyte layer of the electrochromic sheet is solid or gel.
[0590] [8] The electrochromic sheet according to any one of [1] to [7], wherein,
[0591] electrochromic layers are respectively provided on the upper and lower surfaces of the electrolyte layer of the electrochromic sheet.
[0592] [9] The electrochromic sheet according to any one of [1] to [8], wherein,
[0593] the electrochromic sheet further includes an electrode layer between the support layer and the electrochromic layer.
[0594]
[10] An electrochromic device that uses the electrochromic sheet according to any one of [1] to [9].
[0595] <Reference Method 4>
[0596] According to Reference Method 4, by using a metal paste and a liquid sealing material in combination, the adhesion between the columnar electrode and the sealing portion can be improved.
[0597] [1] A method for manufacturing an electrochromic sheet, wherein,
[0598] The electrochromic sheet includes:
[0599] An electrolyte layer;
[0600] An electrochromic layer provided on at least one surface of the electrolyte layer;
[0601] A sealing portion provided to cover the side surfaces of the electrolyte layer and the electrochromic layer; and
[0602] A columnar conductive portion that penetrates the thickness direction of the sealing portion and is electrically connected to the electrolyte layer,
[0603] The method for manufacturing the electrochromic sheet includes:
[0604] A step of disposing at least one of the electrolyte layer or the electrochromic layer on a substrate;
[0605] A step of applying a conductive paste on the substrate in a region that does not overlap with the electrolyte layer and / or the electrochromic layer in a top view and applying a liquid sealing material on the substrate so as to surround the outer periphery of the electrolyte layer and / or the electrochromic layer and the outer periphery of the conductive paste;
[0606] A step of curing the sealing material to form the sealing portion; and
[0607] A step of curing the conductive paste to form the columnar conductive portion.
[0608] [2] The method for manufacturing an electrochromic sheet according to [1], wherein,
[0609] The electrochromic sheet further includes an electrode layer,
[0610] In the step of disposing the electrolyte layer on the substrate,
[0611] The electrode layer is disposed on the substrate, and the electrolyte layer is disposed on the electrode layer,
[0612] The electrolyte layer and the columnar conductive portion are electrically connected through the electrode layer by applying the conductive paste in a region on the surface of the electrode layer that does not overlap with the electrolyte layer.
[0613] [3] The manufacturing method of the electrochromic sheet according to [1] or [2], wherein,
[0614] The conductive paste contains one or more of metal powders selected from gold, silver, copper, platinum, nickel, palladium, and their alloys, and conductive carbon fillers.
[0615] [4] The manufacturing method of the electrochromic sheet according to any one of [1] to [3], wherein,
[0616] The viscosity (25 °C) of the sealing material at a shear rate of 10 / s is 500 Pa·s or less.
[0617] [5] The manufacturing method of the electrochromic sheet according to any one of [1] to [4], wherein,
[0618] The electrochromic sheet is clamped by a pair of support bodies,
[0619] In the step of forming the sealing portion,
[0620] By attaching the pair of support bodies, the sealing material is spread to form the sealing portion covering the sides of the electrolyte layer and the electrochromic layer.
[0621] [6] The manufacturing method of the electrochromic sheet according to any one of [1] to [5], wherein,
[0622] The electrolyte layer of the electrochromic sheet is solid or gel.
[0623] [7] The manufacturing method of the electrochromic sheet according to any one of [1] to [6], wherein,
[0624] The electrochromic sheet is provided with the electrochromic layer on the upper and lower surfaces of the electrolyte layer respectively.
[0625] [8] The manufacturing method of the electrochromic sheet according to any one of [1] to [7], wherein,
[0626] The sealing material contains a curable resin.
[0627] [9] A manufacturing method of an electrochromic device, which includes a step of processing the electrochromic sheet obtained by the manufacturing method of the electrochromic sheet according to any one of [1] to [8].
[0628] <Reference mode 5>
[0629] According to Reference mode 5, in a lens having a sheet member laminated on its surface, the sheet member can be accurately laminated on the lens surface.
[0630] [1] A lens manufacturing method, which manufactures a lens 30 by injecting and filling a lens resin material 34 into a mold 40, the lens manufacturing method comprising:
[0631] A step of disposing a sheet member (bending sheet 120) laminated on the surface (lens convex surface 38) of the lens 30 (lens body) in the cavity 43 of the mold 40; and
[0632] A step of injecting and filling the lens resin material 34 into the cavity 43 in which the sheet member (bending sheet 120) is disposed,
[0633] A positioning structure 80 (positioning angle 137, positioning recess 47) for aligning the position of the sheet member (bending sheet 120) in the cavity 43 is provided in the sheet member (bending sheet 120) and the cavity 43.
[0634] [2] The lens manufacturing method according to [1], wherein
[0635] The positioning structure 80 has a convex portion (positioning angle 137) protruding in the outer peripheral direction of the sheet member (bending sheet 120) and a concave portion (positioning recess 47) for embedding the convex portion (positioning angle 137) in the cavity 43.
[0636] [3] The lens manufacturing method according to [1] or [2], wherein
[0637] The portion of the sheet member (bending sheet 120) laminated on the lens 30 (bending convex surface 36) is formed as a curved surface.
[0638] [4] The lens manufacturing method according to [2] or [3], wherein
[0639] The sheet member (bending sheet 120) has a substantially rectangular shape,
[0640] The convex portions (positioning angles 137) are respectively provided on opposite sides (right side 157, left side 158) of the substantially rectangular shape.
[0641] [5] The lens manufacturing method according to [4], wherein
[0642] The convex portions (positioning angles 137) are provided on the short sides (right side 157, left side 158) of the substantially rectangular shape.
[0643] [6] The lens manufacturing method according to [5], wherein
[0644] One convex portion (positioning angle 137) is provided at each of opposite positions on the short side (right side 157, left side 158).
[0645] [7]The lens manufacturing method according to any one of [2] to [6], wherein,
[0646] The convex portion (positioning angle 137) is provided at a position orthogonal to the flow direction of the lens resin material 34 in the cavity 43.
[0647] [8]The lens manufacturing method according to any one of [1] to [7], wherein,
[0648] The lens resin material 34 is a polycarbonate resin.
[0649] [9]The lens manufacturing method according to any one of [1] to [8], wherein,
[0650] The sheet member (bending sheet 120) is an electrochromic sheet (electronically dimmable sheet) capable of reversibly controlling color display and color erasure by electricity.
[0651]
[10] A lens manufactured by the lens manufacturing method according to any one of [1] to [9] and having a sheet member (bending sheet 120) on its surface (curved convex surface 36).
[0652]
[11] A sheet member (bending sheet 120) that is disposed in an injection molding die 40 and laminated on the surface (curved convex surface 36) of a lens 30 when the lens 30 is manufactured by injection molding, wherein,
[0653] The sheet member (bending sheet 120, electrochromic sheet 150) has a positioning structure 80 for positioning in the die 40 when disposed in the die 40.
[0654]
[12] The sheet member (bending sheet 120, electrochromic sheet 150) according to
[11] , wherein,
[0655] The positioning structure 80 has a convex portion (positioning angle 137) protruding in the outer peripheral direction of the sheet member (bending sheet 120),
[0656] The convex portion (positioning angle 137) is fitted into a positioning structure (positioning recess 47) provided in the die 40.
[0657]
[13] The sheet member (bending sheet 120) according to
[11] or
[12] , wherein,
[0658] The portion laminated on the lens 30 is formed into a curved surface.
[0659]
[14] The sheet member according to
[12] , wherein,
[0660] The sheet member (bending sheet 120, electrochromic sheet 150) has a substantially rectangular shape,
[0661] The convex portions (positioning corners 137) are respectively provided on the opposite sides (right side 157, left side 158) of the substantially rectangular shape.
[0662]
[15] The sheet member according to
[14] , wherein,
[0663] The convex portions (positioning corners 137) are provided on the short sides (right side 157, left side 158) of the substantially rectangular shape.
[0664]
[16] The sheet member according to
[15] , wherein,
[0665] One convex portion (positioning corner 137) is provided at each of the opposite positions on the short sides (right side 157, left side 158).
[0666]
[17] The sheet member according to any one of
[11] to
[16] , wherein,
[0667] The convex portions (positioning corners 137) are provided at positions orthogonal to the flow direction of the lens resin material 34 in the cavity 43 of the mold 40.
[0668]
[18] The sheet member according to any one of
[11] to
[17] , wherein,
[0669] The sheet member (bending sheet 120, electrochromic sheet 150) is an electrochromic sheet (electrochromic sheet 150) capable of reversibly controlling color development and color erasure by electricity.
[0670] Examples
[0671] Next, the present invention will be described in detail by way of examples, but the content of the present invention is not limited to the examples.
[0672] <Experiment 1>
[0673] (1) Preparation of gel electrolyte
[0674] The following materials were prepared.
[0675] · Adhesive resin 1; acrylic urethane (trade name: UXF4002, manufactured by Nippon Kayaku Co., Ltd.)
[0676] · Adhesive resin 2; cross-linked body of polymer having a polymethyl methacrylate (PMMA) chain (trade name: AA-6, manufactured by Toagosei Co., Ltd.)
[0677] · Ionic liquid 1; (EMIMFSI, ethylmethylimidazolium bisfluorosulfonylimide, manufactured by Kanto Chemical Co., Inc.)
[0678] <Example 1-1>
[0679] A solution obtained by mixing binder resin 1, binder resin 2, and ionic liquid 1 in the proportions shown in Table 1 and further mixing a photopolymerization initiator (irgacure 184, manufactured by Nippon Kayaku Co., Ltd.) in an amount of 0.5% by mass based on the total amount of binder resins 1 and 2 was coated on the surface of a demolded PET film (NP75C, manufactured by PANAC CO., LTD.), and was laminated with a demolded PET film (NP75A, manufactured by PANAC CO., LTD.), and then ultraviolet (UV) cured to produce a gel electrolyte.
[0680] < Comparative Example 1-1 >
[0681] The contents of binder resins 1 and 2 and ionic liquid 1 were changed to the proportions shown in Table 1, and otherwise, a gel electrolyte was produced in the same manner as in Example 1-1.
[0682] Table 1
[0683]
[0684] (2) Fabrication of electrochromic sheet
[0685] The electrochromic sheet shown in Figure 1 was fabricated according to the following steps.
[0686] - Formation of the first electrode -
[0687] As the first support, a polycarbonate resin substrate (Polyca Ace, heat deflection temperature 140°C, manufactured by Sumitomo Bakelite Co., Ltd.) with a thickness of 0.5 mm was prepared.
[0688] A first electrode was formed by forming an ITO film with a thickness of about 100 nm on the first support by sputtering.
[0689] 3 g of titanium oxide (manufactured by ISHIHARA SANGYO KAISHA, LTD., ST-21), 0.2 g of acetylacetone, 0.3 g of a surfactant (manufactured by FUJIFILM Wako Pure Chemical Corporation, polyoxyethylene octylphenyl ether), 5.5 g of water, and 1.0 g of ethanol were subjected to bead milling for 12 hours.
[0690] 1.2 g of polyethylene glycol (#20000, manufactured by NOF CORPORATION) was added to the obtained dispersion to prepare a paste.
[0691] By the screen printing method, the obtained paste was coated on the first electrode until the thickness reached 2 μm, dried at 80 °C, and then subjected to UV ozone treatment at 90 °C for 20 minutes, thereby forming an electron transport layer composed of a porous titanium oxide particle film.
[0692] - Formation of the first electrochromic layer -
[0693] Next, a 2,2,3,3-tetrafluoropropanol solution containing 1.5% by mass of a reduced-coloring electrochromic compound I represented by the following chemical formula (EC1) was coated by spin coating, and then annealed at 80 °C for 10 minutes, thereby loading (adsorbing) it on the above-mentioned porous titanium oxide particle film to form the first electrochromic layer.
[0694]
[0695] - Formation of the second electrode -
[0696] As the second support, a polycarbonate resin substrate having the same shape and the same thickness as the above-mentioned first support was prepared. A second electrode was formed by forming an ITO film with a thickness of about 100 nm on the second support by sputtering.
[0697] - Formation of the second electrochromic layer -
[0698] On the ITO film as the second electrode, a solution prepared by mixing polyethylene glycol diacrylate (manufactured by Nippon Kayaku Co., Ltd., PEG400DA), a photoinitiator (manufactured by BASF, IRGACURE 184), a radical polymerizable compound II having a triarylamine represented by the following formula (EC2) as an oxidation-coloring electrochromic material, and 2-butanone in a mass ratio of (57:3:140:800) was prepared.
[0699] Then, the prepared solution was coated on the ITO glass substrate by spin coating.
[0700]
[0701] (In the formula, Me represents a methyl group)
[0702] Next, in a nitrogen atmosphere, UV curing was carried out through a quartz substrate with a Cr layer pattern to selectively form a patterned second electrochromic layer with a thickness of 1.2 μm containing the compound represented by the above radical polymerizable compound II on the second electrode.
[0703] - Lamination process -
[0704] Regarding each of the gel electrolytes produced in the above (1), the release film was peeled off, and the surface of the first electrochromic layer was subjected to a bonding process.
[0705] Next, by means of dispensing, the prepared sealing material (epoxy acrylate resin (“Photolec S-WF17” manufactured by SEKISUIMATERIAL SOLUTIONS CO., LTD.)) was coated so as to surround the side periphery of the first electrochromic layer.
[0706] Then, by aligning and spreading the second electrochromic layer of the second support body with the surface of the gel electrolyte and spreading the sealing material, the side surfaces of the first electrochromic layer and the second electrochromic layer were covered with the sealing material, and ultraviolet rays of 3 J / cm 2 were irradiated (temporarily cured), and heat curing treatment (formally cured) was carried out at 100 °C for 1 hour to cure the sealing material to form a sealing portion, thereby manufacturing an electrochromic sheet.
[0707] (3) Measurement / Evaluation
[0708] Next, the following measurements / evaluations were carried out on the obtained electrochromic sheet of Example 1-1. The results are shown in Table 2.
[0709] · Measurement of deformation amount
[0710] The deformation amount was measured according to the following steps i and ii. And, the displacement-load curve with the horizontal axis being the displacement amount (mm) and the vertical axis being the load (N) is shown in Figure 16 .
[0711] Step i: Using this electrochromic sheet, a test piece (60 × 80 mm; oval) with the electrolyte layer as the central part and the sealing part as the outer edge was manufactured, and both ends of the test piece were clamped with a clamping part, and the central part of the test piece was pressed at 30 N for 30 seconds, and the depth difference between the central part of the test piece before pressing and the central part of the test piece after pressing was taken as the variation amount (mm).
[0712] Step ii: Using this electrochromic sheet, a test piece (60 × 80 mm; oval) with the electrolyte layer as the central part and the sealing part as the outer edge was manufactured, and both ends of the test piece were clamped with a clamping part, and the central part of the test piece was pressed at 50 N for 30 seconds, and the depth difference between the central part of the test piece before pressing and the central part of the test piece after pressing was taken as the variation amount (mm).
[0713] In all steps, a steel ball indentation test was carried out using a measuring machine TENSILON RTF-2430 (manufactured by ORIENTEC CO., LTD.), and the steel ball diameter was set to The test was carried out under the conditions of a load speed of 0.1 mm / min (crosshead speed), a creep load of 30 N or 50 N, a creep time of 30 seconds, and room temperature.
[0714] (4) Evaluation
[0715] The processability of the obtained electrochromic sheet was evaluated. The results are shown in Table 2.
[0716] · Processability
[0717] The outer peripheral cutting process of the electrochromic sheet was carried out while clamping the central part of the electrochromic sheet. Then, the presence or absence of marks was evaluated according to the following criteria. The absence of observed marks indicates good processability of the electrochromic sheet.
[0718] [Evaluation Criteria]
[0719] OK: No marks were observed
[0720] NG: Marks were observed
[0721] Table 2
[0722] Example 1 - 1 Comparative Example 1 - 1 Displacement after 30 s at 30 N [mm] 0.07 0.11 Displacement after 30 s at 50 N [mm] 0.08 0.12 Yield point [N] >50 10 Workability - OK NG
[0723] <Experiment 2>
[0724] (1) Measurement of absorbance
[0725] Using a UV-Vis-NIR spectrophotometer (V-670, manufactured by JASCO Corporation), the absorbance of laminate A at a wavelength of 320 nm was set as α, and the absorbance at a wavelength of 295 nm was set as β, and (β - α) was calculated. Multiple laminates A were prepared, and the value of (β - α) was set as the average value. In addition, the value of α was 1 or less.
[0726] <Example 2-1>
[0727] (2) Fabrication of electrochromic sheet
[0728] - Formation of the second electrode -
[0729] As the second support, a polycarbonate resin substrate with a thickness of 0.5 mm (Polyca Ace, heat deflection temperature 140 °C, manufactured by Sumitomo Bakelite Co., Ltd.) was prepared.
[0730] A second electrode was formed by depositing an ITO film with a thickness of about 100 nm on the second support by sputtering.
[0731] - Formation of the second electrochromic layer -
[0732] 5.50 g of tin oxide sol solution (manufactured by Nissan Chemical Corporation, Ltd., Cernax (セルナックス) CX-S510M), 1.00 g of ethyl cellulose (10 cp, 10 wt%, ethanol solution), 0.50 g of tin(IV) tetra(t-butoxide), and 9.05 g of terpineol were mixed, and after being treated with an ultrasonic homogenizer for 2 minutes, the volatile components were removed with an evaporator to obtain the target paste.
[0733] By the screen printing method, the obtained paste was coated on the second electrode until the thickness became 2 μm, dried at 80 °C, and then subjected to UV ozone treatment at 90 °C for 20 minutes, thereby forming a layer composed of a porous tin oxide particle film.
[0734] Next, after coating a 2,2,3,3-tetrafluoropropanol solution containing 1.5 mass% of the reduction color-developing electrochromic compound I represented by the chemical formula (EC1) by the spin coating method, an annealing treatment was performed at 80 °C for 10 minutes, thereby supporting (adsorbing) it on the above-mentioned porous tin oxide particle film to form a second electrochromic layer, which was used as "laminate A".
[0735] - Formation of the first electrode -
[0736] As the first support, a polycarbonate resin substrate having the same shape and the same thickness as the above-mentioned second support was prepared. By the sputtering method, an ITO film with a thickness of about 100 nm was formed on the first support to form the first electrode.
[0737] - Formation of the first electrochromic layer -
[0738] On the ITO film as the first electrode, a solution prepared by mixing polyethylene glycol diacrylate (manufactured by Nippon Kayaku Co., Ltd., PEG400DA), a photoinitiator (manufactured by BASF Corporation, IRGACURE 184), a radical polymerizable compound II having a triarylamine represented by the formula (EC2) as an oxidation color-developing electrochromic material, and 2-butanone in a mass ratio of (57:3:140:800) was prepared. Then, the prepared solution was coated on the ITO glass substrate by the spin coating method.
[0739] Next, in a nitrogen atmosphere, through a quartz substrate with a Cr layer pattern, UV curing was performed to selectively form a patterned first electrochromic layer with a thickness of 1.2 μm containing the compound represented by the above-mentioned radical polymerizable compound II on the second electrode.
[0740] - Preparation of the gel electrolyte -
[0741] A solution obtained by mixing a polymerizable material (V3877, manufactured by Daido Chemical Corporation) and an electrolyte (1-ethyl-3-methylimidazolium tetracyanoborate (EMIMTCB)) in a mass ratio of (20:80) and further mixing a photoinitiator (irgacure184, manufactured by Nippon Kayaku Co., Ltd.) at 0.5% by mass relative to the polymerizable material was coated on the surface of a demolded PET film (NP75C, manufactured by Fanac Corporation), laminated with a demolded PET film (NP75A, manufactured by Fanac Corporation), and ultraviolet (UV) cured to produce a gel electrolyte.
[0742] - Laminating process -
[0743] Regarding the produced gel electrolyte, the release film was peeled off and a lamination process was performed on the surface of the first electrochromic layer.
[0744] Next, a sealing material (epoxy acrylate resin (“Photolec S-WF17”, manufactured by Sekisui Materials Solutions Co., Ltd.)) was coated by a dispensing method so as to surround the side periphery of the first electrochromic layer.
[0745] Then, by aligning and spreading the second electrochromic layer of the second support body with the surface of the gel electrolyte and spreading the sealing material, the sides of the first electrochromic layer and the second electrochromic layer were covered with the sealing material, irradiated (temporarily cured) with ultraviolet rays of 3 J / cm 2 and heat-cured (formally cured) at 100 °C for 1 hour to cure the sealing material and form a sealing portion, thereby producing an electrochromic sheet.
[0746] <Comparative Example 2-1>
[0747] When forming the second electrochromic layer, the annealing treatment after coating a 2,2,3,3-tetrafluoropropanol solution containing 1.5% by mass of the reduction-developing electrochromic compound I by spin coating was changed to vacuum drying at 40 °C for 30 minutes, and the rest was the same as in Example 2-1.
[0748] (3) Evaluation
[0749] The obtained electrochromic sheets were evaluated as follows. The results are shown in Table 3.
[0750] · Color development and bleaching ability
[0751] The total transmittance when the electrochromic sheet was colored by applying a voltage of 1.6 V for 20 seconds was measured using an ultraviolet-visible-near-infrared spectrophotometer (V-670, manufactured by JASCO Corporation). A low total transmittance during coloring indicates a dark coloration and sufficient colorability was obtained.
[0752] Table 3
[0753] Example 2 - 1 Comparative Example 2 - 1 β-α 1.1 0.7 Total light transmittance when transparent 80% 80% Total light transmittance when colored 10% 50%
[0754] <Experiment 3>
[0755] <Example 3-1>
[0756] (1) Preparation of sealing materials
[0757] The following sealing materials were prepared.
[0758] · Sealing material 1; Epoxy acrylate resin (“Photolec S-WF17”, manufactured by Sekisui Materials Solutions Co., Ltd.), without heat treatment
[0759] · Sealing material 2; Obtained by heat-treating epoxy acrylate resin (“Photolec S-WF17”, manufactured by Sekisui Materials Solutions Co., Ltd.) at 50 °C.
[0760] · Sealing material 3; Epoxy acrylate resin (“Photolec SUR-137”, manufactured by Sekisui Materials Solutions Co., Ltd.), without heat treatment
[0761] The viscosity of each sealing material was measured according to the following procedure. The results are shown in Table 1.
[0762] Using ARES manufactured by TA Instruments, with a combination of a cone plate and a parallel plate, the viscosity of the sealing material was measured at a shear rate of 0.1 / s and 10 / s (25 °C) with a gap of 0.053 mm.
[0763] (2) Fabrication of electrochromic sheet
[0764] The electrochromic sheet shown in Figure 1 was fabricated according to the following procedure.
[0765] - Formation of the first electrode -
[0766] As the first support, a polycarbonate resin substrate with a thickness of 0.5 mm (Polyca Ace, heat deflection temperature 140 °C, manufactured by Sumitomo Bakelite Co., Ltd.) was prepared.
[0767] A first electrode was formed by depositing an ITO film with a thickness of approximately 100 nm on the first support by sputtering.
[0768] 3 g of titanium oxide (manufactured by Ishihara Sangyo Co., Ltd., ST-21), 0.2 g of acetylacetone, 0.3 g of a surfactant (manufactured by Wako Pure Chemical Industries, Ltd., polyoxyethylene octylphenyl ether), 5.5 g of water, and 1.0 g of ethanol were subjected to bead milling for 12 hours.
[0769] 1.2 g of polyethylene glycol (#20000, manufactured by NOF Corporation) was added to the obtained dispersion to prepare a paste.
[0770] The obtained paste was coated on the first electrode by screen printing until the thickness reached 2 μm, dried at 80 °C, and then subjected to UV ozone treatment at 90 °C for 20 minutes to form an electron transport layer composed of a porous titanium oxide particle film.
[0771] - Formation of the first electrochromic layer -
[0772] Next, a 2,2,3,3-tetrafluoropropanol solution containing 1.5% by mass of the reduced-coloring electrochromic compound I represented by Chemical Formula (EC1) was coated by spin coating, and then annealed at 80 °C for 10 minutes to support (adsorb) it on the porous titanium oxide particle film to form the first electrochromic layer.
[0773] - Formation of the second electrode -
[0774] As the second support, a polycarbonate resin substrate having the same shape and the same thickness as the first support was prepared. A second electrode was formed by depositing an ITO film with a thickness of approximately 100 nm on the second support by sputtering.
[0775] - Formation of the second electrochromic layer -
[0776] On the ITO film serving as the second electrode, a solution prepared by mixing polyethylene glycol diacrylate (manufactured by Nippon Kayaku Co., Ltd., PEG400DA), a photoinitiator (manufactured by BASF, IRGACURE 184), a radical-polymerizable compound II having triarylamine represented by Formula (EC2) as an oxidation-coloring electrochromic material, and 2-butanone in a mass ratio of (57:3:140:800) was prepared. Then, the prepared solution was coated on the ITO glass substrate by spin coating.
[0777] Next, in a nitrogen atmosphere, through a quartz substrate with a Cr layer pattern, UV curing was performed to selectively form a patterned second electrochromic layer with a thickness of 1.2 μm containing the compound represented by the above radical polymerizable compound II on the second electrode.
[0778] - Fabrication of Gel Electrolyte -
[0779] A solution obtained by mixing a polymerizable material (V3877, manufactured by Daito Kasei Kogyo Co., Ltd.) and an electrolyte (1-ethyl-3-methylimidazolium tetracyanoborate (EMIMTCB)) in a mass ratio of (20:80) and further mixing a photoinitiator (irgacure184, manufactured by Nippon Kayaku Co., Ltd.) at 0.5% by mass relative to the polymerizable material was coated on the surface of a demolded PET film (NP75C, manufactured by Fanak Co., Ltd.), laminated with a demolded PET film (NP75A, manufactured by Fanak Co., Ltd.), and UV cured to fabricate a gel electrolyte.
[0780] - Lamination Process -
[0781] Regarding the fabricated gel electrolyte, the release film was peeled off and a lamination process was performed on the surface of the first electrochromic layer.
[0782] Next, the prepared sealing material 1 was coated by a dispensing method so as to surround the side periphery of the first electrochromic layer.
[0783] Then, by aligning and spreading the second electrochromic layer of the second support body with the surface of the gel electrolyte, the side surfaces of the first electrochromic layer and the second electrochromic layer were covered with the sealing material, irradiated with ultraviolet rays (temporarily cured) at 3 J / cm 2 and thermally cured (formally cured) at 100 °C for 1 hour to cure the sealing material and form a sealing portion, thereby fabricating an electrochromic sheet.
[0784] (3) Measurement / Evaluation
[0785] Next, the electrochromic sheet of Example 3-1 obtained was subjected to the following measurement / evaluation. The results are shown in Table 4.
[0786] - Evaluation of Processing Durability -
[0787] Regarding the obtained electrochromic sheet, after performing 3D bending processing at 146 °C using a hot press molding machine to make the radius of curvature 131 mm, cutting processing was performed until the width of the sealing portion on the outer periphery of the electrochromic sheet became 2 mm, and the presence or absence of peeling of the sealing portion was evaluated according to the following evaluation criteria.
[0788] [Evaluation Criteria]
[0789] OK: No peeling
[0790] NG: Peeling occurred
[0791] <Comparative Examples 3-1 to 3-2>
[0792] The sealing material used in the electrochromic sheet of Example 3-1 was changed to the material shown in Table 4, and an electrochromic sheet was produced and measured / evaluated in the same manner as in Example 3-1 except for this change.
[0793] Table 4
[0794] Example 3 - 1 Comparative Example 3 - 1 Comparative Example 3 - 2 Sealing material Sealing material 1 Sealing material 2 Sealing material 3 Viscosity (25°C, shear rate 0.1 / s) 900 Pa·s 1500 Pa·s 600 Pa·s Viscosity (25°C, shear rate 10 / s) 150 Pa·s 250 Pa·s 250 Pa·s Evaluation of processing durability OK NG NG
[0795] <Experiment 4>
[0796] <Example 4-1>
[0797] (1) Preparation of the support layer
[0798] The following support layers were prepared and the light transmittance was measured. The results are shown in Table 5.
[0799] · The first support layer and the second support layer: After mixing 100 parts by mass of bisphenol A polycarbonate (“Iupilon E2000F-N” manufactured by Mitsubishi Gas Chemical Company, Inc.) and 0.35 parts by mass of an ultraviolet absorber (“ADK STAB LA-31G” manufactured by ADEKA), melt-kneading was performed by an extruder and extrusion molding was performed through a T-die to obtain a 300-μm sheet.
[0800] (2) Production of the electrochromic sheet
[0801] The electrochromic sheet shown in Figure 1 was produced according to the following steps.
[0802] - Formation of the first electrode -
[0803] The first electrode was formed by forming an ITO film with a thickness of about 100 nm on the first support prepared in (1) above by sputtering.
[0804] 3 g of titanium oxide (manufactured by Ishihara Sangyo Co., Ltd., ST-21), 0.2 g of acetylacetone, 0.3 g of a surfactant (polyoxyethylene octylphenyl ether manufactured by Wako Pure Chemical Industries, Ltd.) were subjected to bead milling treatment together with 5.5 g of water and 1.0 g of ethanol for 12 hours.
[0805] 1.2 g of polyethylene glycol (#20000, manufactured by NOF Corporation) was added to the obtained dispersion to prepare a paste.
[0806] By the screen printing method, the obtained paste was coated on the first electrode until the thickness became 2 μm. After drying it at 80 °C, UV ozone treatment was carried out at 90 °C for 20 minutes, thereby forming an electron transport layer composed of a porous titanium oxide particle film.
[0807] - Formation of the first electrochromic layer -
[0808] Next, after coating a 2,2,3,3 - tetrafluoropropanol solution containing 1.5 mass% of the reduction - color - developing electrochromic compound I represented by the chemical formula (EC1) by the spin - coating method, an annealing treatment was carried out at 80 °C for 10 minutes, thereby loading (adsorbing) it on the above - mentioned porous titanium oxide particle film to form the first electrochromic layer.
[0809] - Formation of the second electrode -
[0810] By the sputtering method, an ITO film was formed to a thickness of about 100 nm on the second support prepared in the above (1) to form the second electrode.
[0811] - Formation of the second electrochromic layer -
[0812] On the ITO film as the second electrode, a solution was prepared by mixing polyethylene glycol diacrylate (manufactured by Nippon Kayaku Co., Ltd., PEG400DA), a photoinitiator (manufactured by BASF Corporation, IRGACURE 184), a radical - polymerizable compound II having triarylamine represented by the formula (EC2) as an oxidation - color - developing electrochromic material, and 2 - butanone in a mass ratio of (57:3:140:800). Then, the prepared solution was coated on the ITO glass substrate by the spin - coating method.
[0813] Next, in a nitrogen atmosphere, through a quartz substrate with a Cr layer pattern, UV curing was carried out to selectively form a patterned second electrochromic layer with a thickness of 1.2 μm containing the compound represented by the above - mentioned radical - polymerizable compound II on the second electrode.
[0814] - Preparation of the gel electrolyte -
[0815] A solution obtained by mixing a polymerizable material (V3877, manufactured by Daito Kasei Kogyo Co., Ltd.) and an electrolyte (1-ethyl-3-methylimidazolium tetracyanoborate (EMIMTCB)) in a mass ratio of (20:80) and further mixing a photoinitiator (irgacure184, manufactured by Nippon Kayaku Co., Ltd.) at 0.5% by mass relative to the polymerizable material was coated on the surface of a demolded PET film (NP75C, manufactured by Fanac Corporation), laminated with a demolded PET film (NP75A, manufactured by Fanac Corporation), and UV-cured to produce a gel electrolyte.
[0816] - Lamination process -
[0817] Regarding the produced gel electrolyte, the release film was peeled off and a lamination process was performed on the surface of the first electrochromic layer.
[0818] Next, a sealing material (epoxy resin "CRM-1576AW", manufactured by Sumitomo Bakelite Co., Ltd.) was coated by a dispensing method so as to surround the side periphery of the first electrochromic layer.
[0819] Then, by aligning and laminating the second electrochromic layer of the second support body with the surface of the gel electrolyte and spreading the sealing material, the side surfaces of the first electrochromic layer and the second electrochromic layer were covered with the sealing material, and a heat curing treatment was performed at 100 °C for 1 hour to cure the sealing material and form a sealing portion, thereby producing an electrochromic sheet.
[0820] (3) Evaluation / Measurement
[0821] The light resistance of the obtained electrochromic sheet was evaluated.
[0822] · Light resistance
[0823] A voltage of 1.6 V was applied to the electrochromic sheet for 15 seconds to cause it to color, and the transmittance was measured. Then, in accordance with ISO12311:2013, in an environment of 28 °C, a xenon lamp with a light quantity of 450 W was irradiated for 51 hours for a light resistance test. Then, after temporarily decoloring the electrochromic sheet, a voltage of 1.6 V was applied again for 15 seconds to cause it to color, the transmittance was measured again, and the difference in the transmittance at the time of coloring before and after the light resistance test was determined.
[0824] The smaller the difference in the transmittance at the time of coloring before and after the light resistance test, the better the light resistance.
[0825] In addition, a UV-visible near-infrared spectrophotometer (V-670, manufactured by JASCO Corporation) was used to measure the transmittance.
[0826] · Measurement of transmittance
[0827] The transmittance of each support layer was measured using a UV-visible near-infrared spectrophotometer (V-670, manufactured by JASCO Corporation), and the light transmittance was calculated. The measurement wavelength was set to 280 nm to 780 nm.
[0828] The results are shown in Figure 17 (Example 4-1), Figure 18 (Comparative Example 4-1).
[0829] <Comparative Example 4-1>
[0830] Except that the ultraviolet absorber ("ADKSTAB LA-31G" manufactured by ADEKA Corporation) was not used in the first support layer and the second support layer, it was carried out in the same manner as in Example 4-1.
[0831] Table 5
[0832] Example 4 - 1 Comparative Example 4 - 1 Transmittance of the first support layer and the second support layer at a wavelength of 380 nm 4% 87% Transmittance of the first support layer and the second support layer at a wavelength of 430 nm 89% 89% Transmittance of the electrochromic sheet when colored before the light resistance test 10% 10% Transmittance of the electrochromic sheet when colored after the light resistance test 13% 19% Difference in transmittance of the electrochromic sheet when colored before and after the light resistance test 3% 9%
[0833] <Experiment 5>
[0834] (1) Preparation of sealing material and conductive material
[0835] (Sealing material)
[0836] · Liquid sealing material 1; epoxy acrylate resin ("Photolec S-WF17" manufactured by Sekisui Materials Solutions Co., Ltd.), viscosity at a shear rate of 10 / s (25 °C) is 150 Pa·s
[0837] · Solid sealing material 2; double-sided adhesive film ("LA-50" manufactured by Nitto Denko Corporation)
[0838] Epoxy acrylate resin ("Photolec S-WF17" manufactured by Sekisui Materials Solutions Co., Ltd.)
[0839] (Conductive material)
[0840] · Conductive paste 1; conductive paste ("DOTITE XA-910" manufactured by Fujikura Kasei Co., Ltd.)
[0841] · Solid conductive material 2; conductive carbon double-sided tape (manufactured by Nissin EM Co., Ltd.)
[0842] (2) Fabrication of electrochromic sheet
[0843] <Example 5-1>
[0844] The electrochromic sheet as shown in Figure 3 was fabricated according to the following steps.
[0845] - Formation of the first electrode -
[0846] As the first support, a polycarbonate resin substrate (Polyca Ace, heat deflection temperature 140 °C, manufactured by Sumitomo Bakelite Co., Ltd.) with a thickness of 0.5 mm was prepared.
[0847] A first electrode was formed by depositing an ITO film with a thickness of approximately 100 nm on the first support by sputtering.
[0848] 3 g of titanium oxide (manufactured by Ishihara Sangyo Co., Ltd., ST - 21), 0.2 g of acetylacetone, 0.3 g of a surfactant (manufactured by Wako Pure Chemical Industries, Ltd., polyoxyethylene octylphenyl ether), 5.5 g of water, and 1.0 g of ethanol were subjected to bead milling for 12 hours.
[0849] 1.2 g of polyethylene glycol (#20000, manufactured by NOF Corporation) was added to the obtained dispersion to prepare a paste.
[0850] The obtained paste was coated on the first electrode by screen printing until the thickness reached 2 μm, dried at 80 °C, and then subjected to UV - ozone treatment at 90 °C for 20 minutes to form an electron transport layer composed of a porous titanium oxide particle film.
[0851] - Formation of the first electrochromic layer -
[0852] Next, a 2,2,3,3 - tetrafluoropropanol solution containing 1.5 mass% of the reduction - color - developing electrochromic compound I represented by chemical formula (EC1) was coated by spin - coating, and then annealed at 80 °C for 10 minutes. Thereby, it was supported (adsorbed) on the above - mentioned porous titanium oxide particle film to form the first electrochromic layer.
[0853] - Formation of the second electrode -
[0854] As the second support, a polycarbonate resin substrate having the same shape and the same thickness as the above - mentioned first support was prepared. A second electrode was formed by depositing an ITO film with a thickness of approximately 100 nm on the second support by sputtering.
[0855] - Formation of the second electrochromic layer -
[0856] On the ITO film serving as the second electrode, a solution was prepared by mixing polyethylene glycol diacrylate (manufactured by Nippon Kayaku Co., Ltd., PEG400DA), a photoinitiator (manufactured by BASF, IRGACURE 184), a radical polymerizable compound II having a triarylamine represented by the formula (EC2) as an oxidative color-developing electrochromic material, and 2-butanone in a mass ratio of (57:3:140:800). Then, the prepared solution was coated on an ITO glass substrate by a spin coating method.
[0857] Next, in a nitrogen atmosphere, UV curing was performed through a quartz substrate with a Cr layer pattern to selectively form a patterned second electrochromic layer with a thickness of 1.2 μm containing the compound represented by the above radical polymerizable compound II on the second electrode.
[0858] - Fabrication of Gel Electrolyte -
[0859] A solution obtained by mixing a polymerizable material (V3877, manufactured by Daido Kasei Kogyo Co., Ltd.) and an electrolyte (1-ethyl-3-methylimidazolium tetracyanoborate (EMIMTCB)) in a mass ratio of (20:80) and further mixing 0.5% by mass of a photopolymerization initiator (irgacure184, manufactured by Nippon Kayaku Co., Ltd.) with respect to the polymerizable material was coated on the surface of a demolded PET film (NP75C, manufactured by Fanak Co., Ltd.), laminated with a demolded PET film (NP75A, manufactured by Fanak Co., Ltd.), and UV-cured to fabricate a gel electrolyte.
[0860] Regarding the fabricated gel electrolyte, the release film was peeled off and laminated on the surface of the first electrochromic layer.
[0861] - Coating Process of Sealing Material and Conductive Paste -
[0862] Next, conductive paste 1 (“DOTITE XA - 910”, manufactured by Fujikura Kasei Co., Ltd.) was coated at two positions on the first electrode provided with the first electrochromic layer and near the periphery of the gel electrolyte and the first electrochromic layer.
[0863] Next, a liquid sealing material 1 (“Photolec S - WF17”, manufactured by Sekisui Materials Solutions Co., Ltd.) was coated by a dispensing method so as to surround the side periphery of the gel electrolyte and the first electrochromic layer and surround the above conductive paste 1.
[0864] - Lamination and Curing Process -
[0865] Then, by aligning and laying the second electrochromic layer of the second support body with the surface of the gel electrolyte and spreading the liquid sealing material 1 and the conductive paste 1, while covering the sides of the first electrochromic layer and the second electrochromic layer with the liquid sealing material 1, the conductive paste 1 is made to fit closely with the liquid sealing material 1. Further, ultraviolet rays of 3 J / cm 2 are irradiated (temporarily cured), and a thermal curing treatment (formally cured) is performed at 100 °C for 1 hour, so that the liquid sealing material 1 and the conductive paste 1 are cured together to form a sealing portion and each columnar conductive portion, thereby manufacturing an electrochromic sheet.
[0866] <Comparative Example 5-1>
[0867] Instead of the liquid sealing material 1 of Example 5-1, a solid sealing material 2 was used, and a part of the manufacturing process was changed as follows. Except for this, an electrochromic sheet was manufactured in the same manner as in Example 5-1.
[0868] Specifically, in the coating process of Example 5-1, instead of coating the liquid sealing material 1, the solid sealing material 2 with holes previously opened in the portions to become columnar conductive portions was attached to the first electrode provided with the first electrochromic layer. Then, the conductive paste 1 was filled into the holes of the solid sealing material 2. Except for this, an electrochromic sheet was manufactured through the fitting and curing processes in the same manner as in Example 5-1. In addition, the solid sealing material 2 was fitted at normal temperature.
[0869] <Comparative Example 5-2>
[0870] Instead of the liquid sealing material 1 of Example 5-1, a solid sealing material 2 was used, and instead of the conductive paste 1, a solid conductive material 2 was used, and a part of the manufacturing process was changed as follows. Except for this, an electrochromic sheet was manufactured in the same manner as in Example 5-1.
[0871] Specifically, in the coating process of Example 5-1, instead of coating the liquid sealing material 1, the solid sealing material 2 with holes previously opened in the portions to become columnar conductive portions was attached to the first electrode provided with the first electrochromic layer. Then, the columnar solid conductive material 2 cut in advance to be able to be filled into the holes of the solid sealing material 2 was attached to the holes of the solid sealing material 2. Then, the second electrochromic layer of the second support body was aligned with the surface of the gel electrolyte, and the solid sealing material 2 and the solid conductive material 2 were fitted at normal temperature, omitting the thermal curing treatment, thereby manufacturing an electrochromic sheet.
[0872] <Comparative Example 5-3>
[0873] Instead of the conductive paste 1 of Example 5-1, a solid conductive material 2 was used, and a part of the manufacturing process was changed as follows. Except for this, an electrochromic sheet was manufactured in the same manner as in Example 5-1.
[0874] Specifically, in the coating process of Example 5-1, the solid conductive material 2 cut into a column shape in advance was attached to the part that becomes the columnar conductive portion, and the liquid sealing material 1 was coated in a dotting manner so as to surround the side periphery of the gel electrolyte and the first electrochromic layer and surround the solid conductive material 2. Then, an electrochromic sheet was produced through the bonding and curing processes in the same manner as in Example 5-1. In addition, the solid conductive material 2 was bonded under normal temperature conditions.
[0875] (3) Evaluation
[0876] The adhesion of each obtained electrochromic sheet was evaluated.
[0877] · Adhesion
[0878] The adhesion of the interface between the sealing portion and the columnar conductive portion of the electrochromic sheet was evaluated. The results are shown in Table 6.
[0879] Table 6
[0880]
[0881] This application claims priority based on Japanese Patent Application No. 2022-174657 filed on October 31, 2022, Japanese Patent Application No. 2022-174669 filed on October 31, 2022, Japanese Patent Application No. 2022-177604 filed on November 4, 2022, Japanese Patent Application No. 2022-174692 filed on October 31, 2022, Japanese Patent Application No. 2022-177608 filed on November 4, 2022, and Japanese Patent Application No. 2022-174841 filed on October 31, 2022, and incorporates the entire contents disclosed therein.
[0882] Explanation of Reference Numerals
[0883] 1 - First support layer, 2 - Second electrode, 3 - First electrochromic layer, 4 - Electrolyte layer, 5 - Second electrochromic layer, 6 - Second electrode, 7 - Second support layer, 8 - Sealing portion, 10 - Electrochromic element, 71 - First auxiliary electrode layer, 72 - First columnar conductive portion, 61 - Second auxiliary electrode layer, 62 - Second columnar conductive portion, 81 - Sealing material, 222 - Conductive paste, 666 - Conductive paste, 511 - Metal nanoparticles, 521 - Electrochromic material, 10 - Electrochromic element, 100 - Electrochromic sheet, 200 - Electrochromic sheet, 11 - First substrate, 12 - Second substrate, 13 - First electrode, 14 - Second electrode, 15 - First auxiliary electrode, 16 - Second auxiliary electrode, 17 - First conductive portion, 18 - Second conductive portion, 20 - Frame, 21 - Frame portion, 22 - Bridging portion, 23 - Temple portion, 24 - Nose pad portion, 25 - Switch, 26 - Battery, 30 - Lens, 35 - Resin layer, 37 - Positioning angle, 137 - Positioning angle, 37a~37k - First positioning angle~Eleventh positioning angle, 40 - Mold, 41 - Upper mold, 42 - Lower mold, 42a - Bending concave surface, 43 - Cavity, 44 - Gate, 45 - Runner, 46 - Resin accumulation portion, 47 - Positioning recess, 50 - Protective film, 51 - Third conductive portion, 52 - Fourth conductive portion, 53 - First hole portion, 54 - Second hole portion, 55 - Sealing portion, 57 - Third hole portion, 58 - Fourth hole portion, 60 - Electrochromic element, 63 - First electrochromic layer, 64 - Second electrochromic layer, 65 - Electrolyte layer, 70 - Colored area, 100 - Sunglasses, 110 - Element sealing connection piece, 120 - Bending piece, 121 - Bending convex surface, 122 - Bending concave surface, 150 - Electrochromic sheet, 210 - Connection piece laminate, 220 - Bending element laminate, 250 - Element laminate.
Claims
1. An electrochromic sheet, comprising: A support layer; An electrolyte layer provided on the support layer; An electrochromic layer provided on at least one surface of the electrolyte layer; and A sealing portion provided to cover at least the side surface of the electrolyte layer, wherein The amount of deformation measured in the following step i is 0.01 mm to 0.09 mm, Step i: Using the electrochromic sheet, a test piece with the electrolyte layer as the central portion and the sealing portion as the outer edge and having a maximum length of 20 mm or more is produced. The two ends of the test piece are clamped by a clamping portion, the central portion of the test piece is pressed at 30 N for 30 seconds, and the depth difference between the central portion of the test piece before pressing and the central portion of the test piece after pressing is taken as the amount of deformation, The unit of the amount of deformation is mm.
2. The electrochromic sheet according to claim 1, wherein The amount of deformation measured in the following step ii is 0.10 mm or less, Step ii: Using the electrochromic sheet, a test piece with the electrolyte layer as the central portion and the sealing portion as the outer edge and having a maximum length of 20 mm or more is produced. The two ends of the test piece are clamped by a clamping portion, the central portion of the test piece is pressed at 50 N for 30 seconds, and the depth difference between the central portion of the test piece before pressing and the central portion of the test piece after pressing is taken as the amount of deformation, The unit of the amount of deformation is mm.
3. The electrochromic sheet according to claim 1, wherein There is no yield point in the step i.
4. The electrochromic sheet according to claim 2, wherein There is no yield point in the step ii.
5. The electrochromic sheet according to claim 1 or 2, wherein The electrolyte layer is solid or gel.
6. The electrochromic sheet according to claim 1 or 2, wherein The electrolyte layer contains an adhesive resin.
7. The electrochromic sheet according to claim 6, wherein The adhesive resin contains one or more selected from (meth)acrylic acid urethane, poly(methyl)acrylate, poly(ethyl)acrylate, and poly(ethylene oxide) acrylate.
8. The electrochromic sheet according to claim 1 or 2, wherein Electrochromic layers are provided on the upper and lower surfaces of the electrolyte layer of the electrochromic sheet respectively.
9. The electrochromic sheet according to claim 1 or 2, wherein The sealing portion is formed using a sealing material containing a curable resin.
10. The electrochromic sheet according to claim 9, wherein The curable resin has at least one selected from an ultraviolet-reactive functional group and a heat-reactive functional group.
11. The electrochromic sheet according to claim 1 or 2, wherein The electrochromic sheet further includes an electrode layer between the support layer and the electrochromic layer.
12. An electrochromic device, wherein It uses the electrochromic sheet according to claim 1 or 2.
Citation Information
Patent Citations
Electrochromic device
JP2007171781A
Electrochromic device
JP2008116718A
Electrochromic element
JP2016045464A
Compound
JP2020138925A
Topical composition
JP2022174657A